Positive active material for all-solid lithium ion battery, electrode and all-solid lithium ion battery

By using lithium metal composite oxide positive electrode active material in all-solid lithium-ion batteries and combining oxide-based solid electrolytes, the problem of poor lithium ion delivery and reception is solved, the discharge rate and circulation characteristics are improved, and the performance of the battery is improved.

CN114982015BActive Publication Date: 2025-01-14TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180009117.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-17
Filing Date
2021-01-15
Publication Date
2025-01-14
Estimated Expiration
2041-01-15

AI Technical Summary

Technical Problem

In all-solid lithium-ion batteries, it is difficult for existing positive electrode active substances to smoothly receive lithium ions between solid electrolytes, resulting in insufficient discharge rate characteristics and failure to effectively utilize the research knowledge of liquid-based lithium-ion secondary batteries.

Method used

The positive electrode active material formed from lithium metal composite oxide has a layered structure and a specific particle size distribution, including lithium and transition metals, is used to combine with oxide-based solid electrolytes to optimize the intercalation and deintercalation process of lithium ions.

Benefits of technology

The discharge rate characteristics and cycle characteristics of all-solid lithium-ion batteries are improved, the high temperature stability and internal resistance of the battery are enhanced, and the output power is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003743231590000431
    Figure BDA0003743231590000431
  • Figure HDA0003743231600000011
    Figure HDA0003743231600000011
  • Figure HDA0003743231600000012
    Figure HDA0003743231600000012
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for an all-solid-state lithium ion battery, which is an all-solid-state lithium ion battery positive electrode active material formed by particles containing crystals of a lithium metal composite oxide, wherein the lithium metal composite oxide has a layered structure and contains at least Li and a transition metal, and the all-solid-state lithium ion battery positive electrode active material satisfies formulas (1) to (3).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode active material for an all-solid lithium ion battery, an electrode and an all-solid lithium ion battery.

[0002] This application claims priority based on Japanese Patent Application No. 2020-006335 filed in Japan on January 17, 2020, the contents of which are incorporated herein by reference. Background Art

[0003] Research on lithium-ion secondary batteries is in full swing for applications such as driving power sources for electric vehicles or household storage batteries. Among them, all-solid lithium-ion secondary batteries have advantages such as high energy density, wide operating temperature range, and low degradation compared to previous lithium-ion secondary batteries using electrolytes. Therefore, all-solid lithium-ion secondary batteries have attracted much attention as a new generation of energy storage devices.

[0004] In the following description, in order to distinguish from an all-solid lithium ion secondary battery, a “conventional lithium ion secondary battery using an electrolyte solution” may be referred to as a “liquid-based lithium ion secondary battery”.

[0005] Patent Document 1 describes the use of LiNi as a positive electrode active material. 1 / 3 Mn 1 / 3 Co 1 / 3 All-solid-state lithium-ion secondary battery for O2. LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 is a material known as a positive electrode active material for liquid lithium ion secondary batteries.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: JP-A-2018-014317 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] In the positive electrode of an all-solid lithium ion secondary battery, lithium ions are transferred between the positive electrode active material and the solid electrolyte. In the research of all-solid lithium ion secondary batteries, a positive electrode active material that can smoothly transfer lithium ions and improve battery performance such as discharge rate characteristics is required.

[0011] In addition, in the research of all-solid lithium ion secondary batteries, there are cases where the research knowledge of conventional liquid lithium ion secondary batteries is not utilized. Therefore, all-solid lithium ion secondary batteries require unique research.

[0012] The present invention is completed in view of this fact, and its purpose is to provide a positive electrode active material for a fully solid lithium ion battery that can smoothly transfer lithium ions between the positive electrode and the solid electrolyte and improve the discharge rate characteristics. In addition, its purpose is to also provide an electrode and a fully solid lithium ion battery having such a positive electrode active material for a fully solid lithium ion battery.

[0013] Here, the "discharge rate characteristic" refers to the ratio of the discharge capacity at 0.01 CA to the discharge capacity at 0.05 CA as 100%. The higher the ratio, the higher the output of the battery, which is better as battery performance.

[0014] Means for solving technical problems

[0015] In order to solve the above-mentioned technical problems, the present invention includes the following aspects.

[0016] [1] A positive electrode active material for an all-solid-state lithium ion battery, which is an all-solid-state lithium ion battery positive electrode active material formed by particles containing crystals of a lithium metal composite oxide, wherein the lithium metal composite oxide has a layered structure and contains at least Li and a transition metal, and the all-solid-state lithium ion battery positive electrode active material satisfies the following formulas (1) to (3):

[0017] 4.5≤(D90 / D10) (1)

[0018] 3.0μm≤D50≤15.0μm (2)

[0019] D max ≤40.0μm (3)

[0020] In the formulas (1) to (3), the particle sizes at which the cumulative proportions from the small particle side reach 10%, 50%, and 90% in the volume-based cumulative particle size distribution curve obtained by laser diffraction particle size distribution measurement are respectively designated as D10, D50, and D90, and D max is the maximum particle size (μm) in the above cumulative particle size distribution curve).

[0021] [2] The positive electrode active material for an all-solid-state lithium ion battery according to [1] above, which is used in an all-solid-state lithium ion battery including an oxide-based solid electrolyte.

[0022] [3] The positive electrode active material for an all-solid-state lithium ion battery according to [1] or [2] above, which satisfies the following formula (1)-1:

[0023] 4.5≤(D90 / D10)<14.0 (1)-1.

[0024] [4] The positive electrode active material for an all-solid-state lithium ion battery according to any one of [1] to [3] above, which satisfies the following formula (4):

[0025] 8.0≤D max / D min ≤40.0 (4)

[0026] (In formula (4), D min is the minimum particle size (μm) in the above cumulative particle size distribution curve).

[0027] [5] The positive electrode active material for an all-solid-state lithium ion battery according to any one of [1] to [4] above, wherein the transition metal is at least one element selected from Ni, Co, Mn, Ti, Fe, V and W.

[0028] [6] The positive electrode active material for an all-solid-state lithium ion battery according to [5] above, wherein the lithium metal composite oxide is represented by the following formula (A):

[0029] Li[Li x (Ni (1-y-z-w) Co y Mn z M w ) 1-x ]O2 (A)

[0030] (M is one or more elements selected from Fe, Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga and V, and satisfies -0.10≤x≤0.30, 0≤y≤0.40, 0≤z≤0.40, 0≤w≤0.10 and 0 <y+z+w)。

[0031] [7] The positive electrode active material for an all-solid-state lithium-ion battery as described in [6] above, wherein the above formula (A) satisfies 1-yzw≥0.50 and y≤0.30.

[0032] [8] A positive electrode active material for a fully solid lithium-ion battery as described in any one of [1] to [7] above, wherein the particles are composed of primary particles, secondary particles that are aggregates of the primary particles, and single particles that exist independently of the primary particles and the secondary particles, and the content of the single particles in the particles is greater than 20%.

[0033] [9] An electrode comprising the positive electrode active material for an all-solid-state lithium ion battery according to any one of [1] to [8] above.

[0034]

[10] The electrode described in [9] above, further comprising a solid electrolyte.

[0035]

[11] An all-solid-state lithium-ion battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, wherein the solid electrolyte layer comprises a first solid electrolyte, the positive electrode comprises a positive electrode active material layer in contact with the solid electrolyte layer, and a current collector stacked with the positive electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode active material for an all-solid-state lithium-ion battery described in any one of [1] to [8].

[0036]

[12] The all-solid-state lithium ion battery described in

[11] above, wherein the positive electrode active material layer comprises the positive electrode active material for the all-solid-state lithium ion battery and a second solid electrolyte.

[0037]

[13] The all-solid-state lithium-ion battery described in

[12] above, wherein the first solid electrolyte and the second solid electrolyte are the same substance.

[0038]

[14] The all-solid-state lithium-ion battery according to any one of

[11] to

[13] above, wherein the first solid electrolyte has an amorphous structure.

[0039]

[15] The all-solid-state lithium-ion battery according to any one of

[11] to

[14] above, wherein the first solid electrolyte is an oxide-based solid electrolyte.

[0040] Effects of the Invention

[0041] According to the present invention, a positive electrode active material for a fully solid lithium ion battery can be provided that can smoothly transfer lithium ions between a positive electrode and a solid electrolyte and can improve discharge rate characteristics. In addition, an electrode and a fully solid lithium ion battery having such a positive electrode active material for a fully solid lithium ion battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Schematic diagram showing a stacked body included in the all-solid-state lithium-ion battery according to the embodiment.

[0043] Figure 2 It is a schematic diagram showing the overall structure of an all-solid-state lithium-ion battery according to an embodiment.

[0044] Figure 3 This is the cumulative particle size distribution curve of the positive electrode active material for the all-solid-state lithium-ion battery manufactured in Example 1. DETAILED DESCRIPTION

[0045] <Positive electrode active material for all-solid-state lithium-ion batteries>

[0046] When a coating layer formed of a metal composite oxide described later is provided on the surface of a particulate lithium metal composite oxide, the particle having the coating layer corresponds to the “particle containing a crystal of a lithium metal composite oxide” in one embodiment of the present invention.

[0047] When there is no coating layer formed of a metal composite oxide on the surface of the lithium metal composite oxide in a particulate form, the lithium metal composite oxide corresponds to the “particles containing crystals of a lithium metal composite oxide” in one embodiment of the present invention.

[0048] The positive electrode active material for all-solid lithium ion batteries is a particle containing crystals of a lithium metal composite oxide. The positive electrode active material for all-solid lithium ion batteries of this embodiment is preferably used in an all-solid lithium ion battery containing an oxide-based solid electrolyte.

[0049] Hereinafter, the positive electrode active material for the all-solid-state lithium ion battery of the present embodiment may be simply referred to as “positive electrode active material”.

[0050] The positive electrode active material satisfies the following requirements.

[0051] (Requirement 1) The lithium metal composite oxide contained in the positive electrode active material has a layered structure and contains at least Li and a transition metal. In addition, the transition metal in this specification refers to a transition metal element.

[0052] (Requirement 2) The particle size distribution satisfies all the following equations (1) to (3),

[0053] 4.5≤(D 90 / D 10 ) (1)

[0054] 3.0μm≤D 50 ≤15.0μm (2)

[0055] D max ≤40.0μm (3)

[0056] In the formulas (1) to (3), the particle sizes at which the cumulative proportions from the small particle side reach 10%, 50%, and 90% in the volume-based cumulative particle size distribution curve obtained by laser diffraction particle size distribution measurement are respectively defined as D 10 , D 50 , D 90 ,

[0057] D max is the maximum particle size in the cumulative particle size distribution curve (μm).

[0058] The following will be described in order.

[0059] (Requirement 1: Lithium metal composite oxide)

[0060] The lithium metal composite oxide contains at least one element selected from the group consisting of Ni, Co, Mn, Ti, Fe, V, and W as a transition metal.

[0061] When the lithium metal composite oxide contains at least one selected from Ni, Co and Mn as a transition metal, the obtained lithium metal composite oxide forms a stable crystal structure in which Li ions can be deintercalated or intercalated. Therefore, when the positive electrode active material is used in the positive electrode of an all-solid lithium ion battery, a high charge capacity and a high discharge capacity can be obtained.

[0062] In addition, when the lithium metal composite oxide contains at least one selected from Ti, Fe, V and W, the crystal structure of the obtained lithium metal composite oxide becomes strong. Therefore, it becomes a positive electrode active material with high thermal stability. In addition, this positive electrode active material can improve the cycle characteristics of the all-solid lithium ion battery.

[0063] More specifically, the lithium metal composite oxide is represented by the following composition formula (A).

[0064] Li[Li x (Ni (1-y-z-w) Co y Mn z M w ) 1-x ]O2 (A)

[0065] (M is one or more elements selected from Fe, Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga, La and V, and satisfies -0.1≤x≤0.30, 0≤y≤0.40, 0≤z≤0.40, 0≤w≤0.10 and 0 <y+z+w)

[0066] (About x)

[0067] From the perspective of obtaining an all-solid lithium ion battery with good cycle characteristics, x is preferably greater than 0, more preferably greater than 0.01, and further preferably greater than 0.02. In addition, from the perspective of obtaining an all-solid lithium ion battery with higher initial coulombic efficiency, x is preferably less than 0.25, and more preferably less than 0.10.

[0068] In this specification, “good cycle characteristics” refers to characteristics in which the battery capacity decreases less due to repeated charge and discharge, and the capacity ratio relative to the initial capacity is less likely to decrease when re-measured.

[0069] In addition, in this specification, "initial coulombic efficiency" refers to the value obtained by "(initial discharge capacity) / (initial charge capacity)×100(%)". A secondary battery with a high initial coulombic efficiency has a small irreversible capacity during initial charge and discharge, and the capacity per unit volume and weight is relatively easy to increase.

[0070] The upper limit and lower limit of x may be arbitrarily combined. x may be -0.10 to 0.25, or -0.10 to 0.10.

[0071] x may be greater than 0 and less than 0.30, greater than 0 and less than 0.25, or greater than 0 and less than 0.10.

[0072] x may be 0.01 to 0.30, 0.01 to 0.25, or 0.01 to 0.10.

[0073] x may be 0.02 to 0.3, 0.02 to 0.25, or 0.02 to 0.10.

[0074] x preferably satisfies 0 <x≤0.30。

[0075] (About y)

[0076] From the viewpoint of obtaining an all-solid lithium ion battery with low internal resistance of the battery, y is preferably greater than 0, more preferably greater than 0.005, further preferably greater than 0.01, and particularly preferably greater than 0.05. In addition, from the viewpoint of obtaining an all-solid lithium ion battery with high thermal stability, y is preferably less than 0.35, more preferably less than 0.33. More preferably less than 0.30.

[0077] The upper limit and lower limit of y may be combined arbitrarily. y may be 0 to 0.35, 0 to 0.33, or 0 to 0.30.

[0078] y may be greater than 0 and less than 0.40, greater than 0 and less than 0.35, greater than 0 and less than 0.33, or greater than 0 and less than 0.30.

[0079] y may be 0.005 to 0.40, 0.005 to 0.35, 0.005 to 0.33, or 0.005 to 0.30.

[0080] y may be 0.01 to 0.40, 0.01 to 0.35, 0.01 to 0.33, or 0.01 to 0.30.

[0081] y can also be 0.05 to 0.40, can also be 0.05 to 0.35, can also be 0.05 to 0.33, can also be 0.05 to 0.30.

[0082] y preferably satisfies 0 < y ≤ 0.40.

[0083] In compositional formula (A), more preferably 0 < x ≤ 0.10, even more preferably 0 < y ≤ 0.40.

[0084] (Regarding z)

[0085] From the viewpoint of obtaining a all-solid-state lithium-ion battery with high cycle characteristics, z is preferably more than 0, more preferably 0.01 or more, further preferably 0.02 or more, and even more preferably 0.1 or more. In addition, from the viewpoint of obtaining a all-solid-state lithium-ion battery with high storage stability at high temperature (for example, in an environment of 60 °C), z is preferably 0.39 or less, more preferably 0.38 or less, and further preferably 0.35 or less.

[0086] The upper and lower limit values of z can be arbitrarily combined. z can be 0 to 0.39, can also be 0 to 0.38, can also be 0 to 0.35.

[0087] z can also be 0.01 to 0.40, can also be 0.01 to 0.39, can also be 0.01 to 0.38, can also be 0.01 to 0.35.

[0088] z can also be 0.02 to 0.40, can also be 0.02 to 0.39, can also be 0.02 to 0.38, can also be 0.02 to 0.35.

[0089] z can also be 0.10 to 0.40, can also be 0.10 to 0.39, can also be 0.10 to 0.38, can also be 0.10 to 0.35.

[0090] z is preferably 0.02 ≤ z ≤ 0.35.

[0091] (Regarding w)

[0092] From the viewpoint of obtaining a all-solid-state lithium-ion battery with low internal resistance of the battery, w is preferably more than 0, more preferably 0.0005 or more, and further preferably 0.001 or more. In addition, from the viewpoint of obtaining a all-solid-state lithium-ion battery with a large discharge capacity at a high current rate, w is preferably 0.09 or less, more preferably 0.08 or less, and further preferably 0.07 or less.

[0093] The upper and lower limit values of w can be arbitrarily combined. w can be 0 to 0.09, can also be 0 to 0.08, can also be 0 to 0.07.

[0094] w may be greater than 0 and less than 0.10, greater than 0 and less than 0.09, greater than 0 and less than 0.08, or greater than 0 and less than 0.07.

[0095] w may also be 0.0005 to 0.10, 0.0005 to 0.09, 0.0005 to 0.08, or 0.0005 to 0.07.

[0096] w may be 0.001 to 0.10, 0.001 to 0.09, 0.001 to 0.08, or 0.001 to 0.07.

[0097] w preferably satisfies 0≤w≤0.07.

[0098] (About y+z+w)

[0099] From the viewpoint of obtaining an all-solid lithium ion battery with a large battery capacity, y+z+w is preferably 0.50 or less, more preferably 0.48 or less, and even more preferably 0.46 or less.

[0100] y+z+w exceeds 0, is preferably 0.001 or more, and is more preferably 0.002 or more.

[0101] It is preferred that y+z+w is greater than 0 and less than or equal to 0.50.

[0102] The lithium metal composite oxide contained in the positive electrode active material preferably satisfies 1-yzw≥0.50 and y≤0.30 in the composition formula (A). That is, the lithium metal composite oxide contained in the positive electrode active material preferably has a Ni content molar ratio of 0.50 or more and a Co content molar ratio of 0.30 or less in the composition formula (A).

[0103] (About M)

[0104] M represents one or more elements selected from Fe, Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga, La and V.

[0105] In addition, from the viewpoint of obtaining an all-solid lithium ion battery with high cycle characteristics, M is preferably one or more elements selected from Ti, Mg, Al, W, B and Zr, and more preferably one or more elements selected from Al and Zr. In addition, from the viewpoint of obtaining an all-solid lithium ion battery with high thermal stability, M is preferably one or more elements selected from Ti, Al, W, B and Zr.

[0106] An example of a preferred combination of x, y, z, and w is that x is 0.02 to 0.30, y is 0.05 to 0.30, z is 0.02 to 0.35, and w is 0 to 0.07. For example, a lithium metal composite oxide in which x=0.05, y=0.20, z=0.30, and w=0, or a lithium metal composite oxide in which x=0.05, y=0.08, z=0.04, and w=0, or a lithium metal composite oxide in which x=0.25, y=0.07, z=0.02, and w=0 can be cited.

[0107] <Composition Analysis>

[0108] The composition of the lithium metal composite oxide can be confirmed by dissolving particles of the positive electrode active material containing the lithium metal composite oxide in hydrochloric acid and then performing composition analysis using an inductively coupled plasma emission spectrometer. The analysis results of Li and transition metals in the positive electrode active material can be regarded as the results of the composition analysis of the lithium metal composite oxide. As an inductively coupled plasma emission spectrometer, for example, SPS3000 manufactured by SII NanoTechnology Co., Ltd. can be used.

[0109] In addition, all-solid-state lithium-ion batteries are charged by applying a negative potential to the positive electrode and a positive potential to the negative electrode using an external power source.

[0110] In addition, the discharge of the all-solid lithium ion battery is carried out by connecting a discharge circuit to the positive and negative electrodes of the charged all-solid lithium ion battery and energizing the discharge circuit. The discharge circuit includes electronic equipment, electrical appliances, and electric vehicles driven by the power of the all-solid lithium ion battery.

[0111] (Layered structure)

[0112] The crystal structure of the lithium metal composite oxide is a layered structure. The crystal structure of the lithium metal composite oxide is more preferably a hexagonal crystal structure or a monoclinic crystal structure.

[0113] The hexagonal crystal structure belongs to P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65 , any one of the space groups including P62, P64, P63, P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mm, P6 / mcc, P63 / mcm and P63 / mmc.

[0114] In addition, the monoclinic crystal structure belongs to any space group selected from P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c and C2 / c.

[0115] Among them, in order to obtain a lithium secondary battery with a high discharge capacity, the crystal structure is particularly preferably a hexagonal crystal structure belonging to the space group R-3m or a monoclinic crystal structure belonging to the space group C2 / m.

[0116] <Method for Confirming Layered Structure>

[0117] The crystal structure can be confirmed by observing the positive electrode active material using a powder X-ray diffraction measuring apparatus. When the positive electrode active material has a coating layer, the crystal structure can be confirmed by observing a material obtained by removing the coating layer by a known method using the above method.

[0118] The powder X-ray diffraction measurement can be performed using an X-ray diffractometer, for example, Ultimal V manufactured by Rigaku Corporation.

[0119] (Requirement 2: Particle size distribution)

[0120] Regarding the above requirement 2, the "volume-based cumulative particle size distribution" can be measured by a measurement method based on the laser diffraction scattering method. The particle size distribution measurement based on the laser diffraction scattering method is called "laser diffraction particle size distribution measurement."

[0121] <Method for measuring cumulative particle size distribution based on volume standard>

[0122] Specifically, the cumulative particle size distribution is measured by the following measurement method.

[0123] First, 0.1 g of the positive electrode active material was added to 50 ml of a 0.2 mass % sodium polyphosphate aqueous solution to obtain a dispersion in which the positive electrode active material was dispersed.

[0124] Next, the obtained dispersion was subjected to particle size distribution measurement using a laser diffraction scattering particle size distribution measuring device to obtain a volume-based cumulative particle size distribution curve. The measurement range of the particle size distribution was 0.02 μm to 2000 μm.

[0125] As a laser diffraction scattering particle size distribution measuring apparatus, for example, Microtrac MT3300EXII manufactured by Microtrac BEL Co., Ltd. can be used.

[0126] In the obtained cumulative particle size distribution curve, when the whole is taken as 100%, the particle size value at the point where the cumulative volume from the fine particle side reaches 10% is taken as the 10% cumulative volume particle size D. 10 The particle size value at the point where 50% of the particles are accumulated is taken as the 50% cumulative volume particle size D 50 The particle size value at the point where 90% of the particles are found is taken as the 90% cumulative volume particle size D 90 (μm).

[0127] In addition, the maximum particle size (i.e., the maximum particle size) in the obtained cumulative particle size distribution curve is taken as D max The minimum particle size (μm) in the cumulative particle size distribution curve is taken as D min (μm).

[0128] [Formula (1)]

[0129] The positive electrode active material satisfies the following formula (1).

[0130] 4.5≤(D 90 / D 10 ) (1)

[0131] The formula (1) is preferably the following formula (1)-1.

[0132] 4.5≤(D 90 / D 10 )<14.0 (1)-1

[0133] D 90 / D 10 It is preferably 5.0 or more, more preferably 6.0 or more, and particularly preferably 7.0 or more.

[0134] D 90 / D 10 It is preferably less than 14.0, more preferably 13.5, particularly preferably 13.2 or less, and particularly preferably 13.0 or less.

[0135] The above upper limit values ​​and lower limit values ​​may be arbitrarily combined.

[0136] As an example of combination, D 90 / D 10 It is preferably 5.0 to 13.5, more preferably 6.0 to 13.2, and particularly preferably 7.0 to 13.0.

[0137] [Formula (2)]

[0138] The positive electrode active material satisfies the following formula (2).

[0139] 3.0μm≤D 50 ≤15.0μm (2)

[0140] D 50 It is preferably 3.5 μm or more, more preferably 4.0 μm or more, and particularly preferably 4.5 μm or more.

[0141] D 50 It is preferably 14.0 μm or less, more preferably 13.0 μm or less, and particularly preferably 12.0 μm or less.

[0142] The above upper limit values ​​and lower limit values ​​may be arbitrarily combined.

[0143] As an example of combination, D 50 Examples include 3.5 μm to 14.0 μm, 4.0 μm to 13.0 μm, and 4.5 μm to 12.0 μm.

[0144] [Formula (3)]

[0145] The positive electrode active material satisfies the following formula (3).

[0146] D max ≤40.0μm (3)

[0147] D max It is preferably 39.5 μm or less, more preferably 39.0 μm or less, and particularly preferably 38.5 μm or less.

[0148] D max It is preferably 20.0 μm or more, more preferably 21.0 μm or more, and particularly preferably 22.0 μm or more.

[0149] The above upper limit values ​​and lower limit values ​​may be arbitrarily combined.

[0150] As an example of combination, D max Examples include 20.0 μm to 40.0 μm, 20.0 μm to 39.5 μm, 21.0 μm to 39.0 μm, and 22.0 μm to 38.5 μm.

[0151] (Other requirements)

[0152] The positive electrode active material further preferably satisfies the following formula (4).

[0153] 8.0≤D max / D min ≤40.0 (4)

[0154] D max / D min It is preferably 8.5 or more, more preferably 9.0 or more, and particularly preferably 9.5 μm or more. max / D min It is preferably 36.0 or less, more preferably 34.0 or less, and particularly preferably 32.0 μm or less.

[0155] The above upper limit values ​​and lower limit values ​​may be arbitrarily combined.

[0156] As an example of combination, D max / D min Examples include 8.5 to 36.0, 9.0 to 34.0, and 9.5 to 32.0.

[0157] In order to adjust the particle size distribution to a desired range, the positive electrode active material may be mixed with two or more lithium metal composite oxides having different particle sizes.

[0158] The inventors' studies have revealed that even positive electrode active materials that exhibit good battery performance when used in positive electrodes of conventional liquid lithium ion secondary batteries may have insufficient performance when used in positive electrodes of all-solid lithium ion batteries.

[0159] Based on the knowledge unique to all-solid lithium ion batteries, the inventors have found during research that a positive electrode active material satisfying the above requirements 1 and 2 exhibits high discharge rate characteristics when used in a positive electrode of an all-solid lithium ion battery.

[0160] First, the positive electrode active material satisfies requirement 1 and can well perform intercalation and deintercalation of lithium ions.

[0161] In addition, in the positive electrode of the all-solid lithium ion battery, the positive electrode active material transfers lithium ions between the positive electrode active material and the solid electrolyte. In this all-solid lithium ion battery, the positive electrode active material having a particle size distribution that satisfies requirement 2 is easy to fill small particles in the gaps between large particles, and the contact area between the positive electrode active materials or between the positive electrode active materials and the solid electrolyte is easy to expand. Therefore, when the positive electrode active material is used in the positive electrode of the all-solid lithium ion battery, the transfer of lithium ions is easy to carry out between the positive electrode active material and the solid electrolyte.

[0162] Therefore, when a positive electrode active material satisfying requirements 1 and 2 is used in a positive electrode of an all-solid-state lithium ion battery, lithium ions can be smoothly transferred between the solid electrolyte and the positive electrode active material, thereby improving the discharge rate characteristics.

[0163] The discharge rate characteristics of the all-solid-state lithium-ion battery can be evaluated by the 0.05CA / 0.01CA discharge capacity ratio obtained by the following method.

[0164] <Manufacturing of all-solid-state lithium-ion batteries>

[0165] (Manufacturing of positive electrode active material sheet)

[0166] The positive electrode active material and Li3BO3 were mixed in a ratio of positive electrode active material: Li3BO3 solvent = 80:20 (molar ratio) to obtain a mixed powder. A resin binder (cellulose acetate), a plasticizer (dioctyl phthalate) and a solvent (acetone) were added to the obtained mixed powder in a ratio of mixed powder: resin binder: plasticizer: solvent = 100:10:10:100 (mass ratio), and mixed using a planetary stirring and degassing device.

[0167] The obtained slurry is degassed using a planetary stirring and degassing device to obtain a positive electrode mixture slurry.

[0168] The obtained positive electrode mixture slurry was applied onto a PET film using a doctor blade, and the applied film was dried to form a positive electrode film having a thickness of 50 μm.

[0169] The positive electrode film was peeled off from the PET film, punched into a circle with a diameter of 14.5 mm, and uniaxially pressed at 20 MPa for 1 minute in the thickness direction of the positive electrode film to obtain a positive electrode active material sheet with a thickness of 40 μm.

[0170] (Manufacturing of all-solid-state lithium-ion batteries)

[0171] Stacking positive electrode active material sheets and Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 Solid electrolyte particles (for example, manufactured by Toyoshima Seisakusho Co., Ltd.) are uniaxially pressed in parallel to the stacking direction to obtain a stacked body.

[0172] A positive electrode current collector (gold foil, 500 μm thick) was further stacked on the positive electrode active material sheet of the obtained laminate, and heated at 300°C for 1 hour under a pressure of 100 gf to burn off the organic components. Furthermore, the temperature was raised to 800°C at 5°C / min, and then sintered at 800°C for 1 hour to obtain a laminate of a solid electrolyte layer and a positive electrode.

[0173] Next, the following operations were performed in a glove box with an argon atmosphere.

[0174] A negative electrode (Li foil, 300 μm thick), a negative electrode collector (stainless steel plate, 50 μm thick), and a corrugated washer (made of stainless steel) were further stacked on the solid electrolyte layer in the stack of the solid electrolyte layer and the positive electrode.

[0175] For the stacked body from the positive electrode to the corrugated gasket, the positive electrode is placed on the lower cover of the coin-type battery R2032 part (produced by Hohsen Co., Ltd.), overlapped on the corrugated gasket, covered with the upper cover, and riveted using a riveting machine to produce an all-solid lithium ion battery.

[0176] <Determination of 0.05CA / 0.01CA Discharge Capacity Ratio>

[0177] Using the all-solid lithium ion battery produced by the above method, an initial charge and discharge test was performed under the following conditions, and then a discharge rate test was performed to calculate the 0.05CA / 0.01CA discharge capacity ratio.

[0178] (Initial charge and discharge test conditions)

[0179] Test temperature: 60℃

[0180] Maximum charging voltage 4.3V, charging current 0.01CA, cut-off current 0.002CA, constant current constant voltage charging

[0181] Minimum discharge voltage 2.5V, discharge current 0.01CA, constant current discharge

[0182] <Discharge rate test>

[0183] Test temperature 60℃

[0184] Maximum charging voltage 4.3V, charging current 0.01CA or 0.05CA, cut-off current 0.002CA, constant current and constant voltage charging

[0185] Minimum discharge voltage 2.5V, discharge current 0.01CA or 0.05CA, constant current discharge

[0186] The discharge capacity when the battery is discharged at a constant current of 0.01 CA and the discharge capacity when the battery is discharged at a constant current of 0.05 CA are used to calculate the 0.05 CA / 0.01 CA discharge capacity ratio obtained by the following formula as an indicator of the discharge rate characteristics. The higher the 0.05 CA / 0.01 CA discharge capacity ratio becomes, the higher the discharge rate characteristics are, and the higher the output power of the lithium secondary battery is.

[0187] 0.05CA / 0.01CA discharge capacity ratio (%) = discharge capacity at 0.05CA / discharge capacity at 0.01CA×100

[0188] (Other components 1)

[0189] The particles constituting the positive electrode active material of the positive electrode active material are preferably composed of primary particles, secondary particles that are aggregates of the primary particles, and single particles that exist independently of the primary particles and the secondary particles.

[0190] <Method for Confirming Particle Shape>

[0191] The “primary particles” refer to particles having no apparent grain boundaries when observed with a scanning electron microscope at a field of view of 20,000 times, and particles having a particle size of less than 0.5 μm.

[0192] The "secondary particles" refer to primary particle aggregates formed by agglomeration of primary particles. When the secondary particles are observed at a field of view of 20,000 times using a scanning electron microscope, crystal boundaries appear to exist.

[0193] The term “single particle” refers to a particle that exists independently of secondary particles, has no apparent grain boundaries when observed with a scanning electron microscope at a field of view of 20,000 times, and has a particle diameter of 0.5 μm or more.

[0194] That is, when the positive electrode active material of the present embodiment is observed with a scanning electron microscope at a field of view of 20,000 times, it is composed of particles that do not appear to have grain boundaries and particles that appear to have grain boundaries.

[0195] The particles having no apparent grain boundaries are composed of "primary particles" having a small particle size and "single particles" having a large particle size, based on a particle size of 0.5 μm.

[0196] The particles having the apparent grain boundaries are "secondary particles" which are aggregated particles of the above-mentioned "primary particles".

[0197] In the positive electrode active material, the content of single particles in the whole particles is preferably 20% or more in terms of the number of particles. When the positive electrode active material with a single particle content of 20% or more in the whole particles is used in a solid-state battery, it is easy to ensure the contact interface with the solid electrolyte in the positive electrode layer, and the conduction of lithium ions through the interface is carried out smoothly.

[0198] In addition, since there are no grain boundaries within the single particles of the positive electrode active material whose content of single particles in the entire particles is more than 20%, even if it is used in the positive electrode of an all-solid lithium-ion battery and is repeatedly charged and discharged, the particles are not prone to cracks and are easy to maintain a conductive path.

[0199] The average particle size of a single particle is preferably 0.5 μm or more, more preferably 1.0 μm or more. The average particle size of a single particle is preferably 10 μm or less, more preferably 5 μm or less.

[0200] The upper limit value and the lower limit value of the average particle size of single particles can be arbitrarily combined.

[0201] The combination of the upper limit value and the lower limit value of the average particle size of single particles may be 0.5 μm to 10 μm and 1.0 μm to 5 μm.

[0202] The average particle size of the secondary particles is preferably 3.0 μm or more, more preferably 5.0 μm or more. The average particle size of the secondary particles is preferably 15 μm or less, more preferably 10 μm or less.

[0203] The upper limit value and the lower limit value of the average particle size of the secondary particles may be arbitrarily combined.

[0204] Examples of a combination of the upper limit and the lower limit of the average particle size of the secondary particles include 3.0 μm to 15 μm and 5.0 μm to 10 μm.

[0205] The average particle diameter of single particles and secondary particles can be measured by the following method.

[0206] First, the positive electrode active material was placed on a conductive sheet attached to a sample stage, and then, using a scanning electron microscope, the positive electrode active material was irradiated with an electron beam having an acceleration voltage of 20 kV and observed at a field of view of 20,000 times.

[0207] As a scanning electron microscope, for example, JSM-5510 manufactured by JEOL Ltd. can be used.

[0208] Next, 50 to 98 single particles or secondary particles are extracted from the obtained electron microscope image (SEM photograph) by the following method.

[0209] (Single Particle Extraction Method)

[0210] When measuring the average particle size of single particles, all single particles contained in one field of view are measured at a magnification of 20,000 times. When the number of single particles contained in one field of view is less than 50, single particles in multiple fields of view with a measurement number of 50 or more are measured.

[0211] (Extraction method of secondary particles)

[0212] When measuring the average particle size of secondary particles, all secondary particles contained in one field of view are taken as the measurement object in a 20,000-fold magnification field of view. When the number of secondary particles contained in one field of view is less than 50, the secondary particles in multiple fields of view with a measurement number of 50 or more are taken as the measurement object.

[0213] For the image of the extracted single particle or secondary particle, the distance between parallel lines drawn from a certain direction when sandwiching the parallel lines (diameter in a certain direction) is measured as the particle size of the single particle or secondary particle.

[0214] The arithmetic mean value of the particle diameters of the obtained single particles or secondary particles is the average particle diameter of the single particles contained in the positive electrode active material or the average particle diameter of the secondary particles contained in the positive electrode active material.

[0215] <Calculation method of single particle content>

[0216] Use a scanning electron microscope to observe the powder of the positive electrode active material at a field of view of 20,000 times, and count the number of single particles and secondary particles in the observed field of view. The number of single particles is N1, the number of secondary particles is N2, and the number ratio of single particles is calculated by N1 / (N1+N2)[%]. In addition, when the number of particles that can be observed is less than 50, obtain multiple continuous fields of view until 50 particles can be confirmed.

[0217] (Other components 2)

[0218] The positive electrode active material preferably has a coating layer formed of a metal composite oxide on the surface of the lithium metal composite oxide constituting the positive electrode active material.

[0219] As the metal composite oxide constituting the covering layer, an oxide having lithium ion conductivity is preferably used.

[0220] Even when the metal composite oxide constituting the coating layer has no lithium ion conductivity, if the coating layer is a very thin film (for example, 0.1nm to 1.0nm), the battery performance is improved compared to the positive electrode active material without a coating layer. At this time, it is speculated that lithium ion conductivity is exhibited in the coating layer. However, the method of attaching a uniform coating layer on the surface of the particles of the lithium metal composite oxide and controlling it to a thickness of 0.1nm to 1.0nm is limited to a method that lacks mass production. As an example of such a manufacturing method that lacks mass production, the ALD (Atomic Laser Deposition) method can be cited.

[0221] On the other hand, when the metal composite oxide constituting the covering layer has lithium ion conductivity, the covering layer preferably conducts lithium ions even if the thickness of the covering layer is about 5 nm to 20 nm, thereby improving battery performance, which is preferred.

[0222] The thickness of the coating layer can be measured by taking the positive electrode active material having the maximum diameter of 50% cumulative volume particle size D50 (μm) ± 5% obtained by laser diffraction particle size distribution measurement as the object, and the arithmetic mean of the values ​​measured for 10 particles is taken as the thickness of the coating layer.

[0223] For the particles of the positive electrode active material to be measured, the average thickness of the coating layer is obtained by using the analysis results of the scanning transmission electron microscope (STEM)-energy dispersive X-ray spectroscopy (EDX). The spectral line profile of the element unique to the coating layer is prepared, and based on the obtained spectral line profile, the range in which the above-mentioned unique element can be detected is used as the existence range of the coating layer, and the thickness of the coating layer can be obtained.

[0224] Examples of such metal composite oxides include metal composite oxides of Li and at least one element selected from Nb, Ge, Si, P, Al, W, Ta, Ti, S, Zr, Zn, V, and B.

[0225] When the positive electrode active material has a coating layer, a high resistance layer is not easily formed at the interface between the positive electrode active material and the solid electrolyte, and a high output power of the all-solid lithium ion battery can be achieved. This effect is particularly easy to obtain in a sulfide-based all-solid battery using a sulfide-based solid electrolyte as the solid electrolyte.

[0226] <Method 1 for producing positive electrode active material>

[0227] When producing a lithium metal composite oxide, first, a metal composite compound containing a metal element other than Li among metal elements constituting the target lithium metal composite oxide is prepared.

[0228] Thereafter, the metal composite compound is preferably mixed with a lithium compound, and the resulting mixture is fired.

[0229] In the present embodiment, it is preferred that the metal composite compound and the lithium compound be fired together with an inactive flux.

[0230] Specifically, the "metal composite compound" is a compound containing Ni as an essential metal element and any one or more elements selected from Co, Mn, Fe, Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga, La and V.

[0231] As the metal composite compound, a metal composite hydroxide or a metal composite oxide is preferable.

[0232] Hereinafter, an example of a method for producing a lithium metal composite oxide will be described by dividing into a production step of a metal composite compound and a production step of a lithium metal composite oxide.

[0233] (Metal Composite Compound Manufacturing Process)

[0234] The metal composite compound can be manufactured by a commonly known coprecipitation method. As the coprecipitation method, a commonly known intermittent coprecipitation method or a continuous coprecipitation method can be used. Hereinafter, as a metal element, a metal composite hydroxide comprising Ni, Co and Mn is taken as an example to describe in detail the manufacturing method of the metal composite compound.

[0235] First, a nickel salt solution, a cobalt salt solution, a manganese salt solution and a complexing agent are reacted by a coprecipitation method, particularly a continuous coprecipitation method described in JP-A-2002-201028, to produce Ni (1-y-z) Co y Mn z A metal composite hydroxide represented by (OH)2 (wherein y+z<1).

[0236] The nickel salt used as the solute of the nickel salt solution is not particularly limited, and for example, any one or two or more of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.

[0237] As the cobalt salt serving as the solute of the cobalt salt solution, for example, one or more of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate may be used.

[0238] As the manganese salt serving as the solute of the manganese salt solution, for example, any one or two or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate may be used.

[0239] The above metal salts correspond to the above Ni (1-y-z) Co y Mn z That is, the molar ratio of nickel in the solute of the nickel salt solution, cobalt in the solute of the cobalt salt solution, and manganese in the solute of the manganese salt solution used for each metal salt corresponds to Ni (1-y-z) Co y Mn zThe composition ratio of (OH)2 reaches (1-yz):y:z.

[0240] In addition, the solvent of the nickel salt solution, the cobalt salt solution, and the manganese salt solution is water.

[0241] The complexing agent is a compound that can form a complex with nickel ions, cobalt ions and manganese ions in aqueous solution. Examples of the complexing agent include ammonium ion donors, hydrazine, ethylenediaminetetraacetic acid, nitrotriacetic acid, lauryl diacetic acid and glycerol. Examples of ammonium ion donors include ammonium salts such as ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate and ammonium fluoride.

[0242] In the manufacturing process of the metal composite hydroxide, a complexing agent may or may not be used. When a complexing agent is used, the amount of the complexing agent contained in the mixed solution comprising the nickel salt solution, the arbitrary metal salt solution and the complexing agent is, for example, in a molar ratio greater than 0 and less than 2.0 relative to the total molar number of the metal salt.

[0243] In this embodiment, the molar ratio of the amount of the complexing agent contained in the mixed solution including the nickel salt solution, the cobalt salt solution, the manganese salt solution and the complexing agent to the total molar number of the metal salt is, for example, greater than 0 and less than 2.0.

[0244] In the coprecipitation method, in order to adjust the pH of the mixed solution containing the nickel salt solution, the optional metal salt solution and the complexing agent, an alkali metal hydroxide is added to the mixed solution before the pH of the mixed solution reaches alkaline to neutral. The alkali metal hydroxide is, for example, sodium hydroxide or potassium hydroxide.

[0245] In addition, the pH value in this specification is defined as a value measured when the temperature of the mixed solution is 40° C. The pH of the mixed solution is measured when the temperature of the mixed solution sampled from the reaction tank reaches 40° C.

[0246] When a complexing agent is continuously supplied to the reaction tank in addition to the above-mentioned nickel salt solution, cobalt salt solution and manganese salt solution, Ni, Co and Mn react to generate Ni (1-y-z) Co y Mn z (OH)2.

[0247] During the reaction, the temperature of the reaction tank is controlled within a range of, for example, 20°C to 80°C, preferably 30°C to 70°C.

[0248] During the reaction, the pH value in the reaction tank is controlled within the range of, for example, pH 9 to pH 13, preferably pH 11 to pH 13.

[0249] The contents in the reaction tank are stirred and mixed appropriately.

[0250] The reaction tank used in the continuous coprecipitation method may be a type of reaction tank that overflows in order to separate the formed reaction precipitate.

[0251] By controlling the metal salt concentration of the metal salt solution supplied to the reaction tank, the stirring speed, the reaction temperature, the reaction pH, and the calcination conditions described below, various physical properties of the finally obtained lithium metal composite oxide, such as the secondary particle size and pore radius, can be controlled.

[0252] In addition to controlling the above conditions, various gases, such as inert gases such as nitrogen, argon, and carbon dioxide, oxidizing gases such as air and oxygen, or mixed gases thereof, may be supplied into the reaction vessel to control the oxidation state of the resulting reaction product.

[0253] As the compound (oxidizing agent) for oxidizing the obtained reaction product, peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorates, hypochlorites, nitric acid, halogens, ozone, and the like can be used.

[0254] As the compound for reducing the obtained reaction product, an organic acid such as oxalic acid and formic acid, a sulfite, hydrazine, etc. can be used.

[0255] Specifically, the reaction tank may be in an inert atmosphere. When the reaction tank is in an inert atmosphere, the metal elements contained in the mixed solution that are more easily oxidized than Ni can be suppressed from agglomerating earlier than Ni. Therefore, a uniform metal composite hydroxide can be obtained.

[0256] In addition, the reaction tank may be in a moderate oxidizing atmosphere. The oxidizing atmosphere may be an oxygen-containing atmosphere in which an oxidizing gas is mixed with an inert gas. By providing a suitable oxidizing atmosphere in the reaction tank where an oxidant may be present in the inert atmosphere, the transition metal contained in the mixed solution is moderately oxidized, making it easy to control the morphology of the metal composite oxide.

[0257] The oxygen or oxidizing agent in the oxidizing atmosphere may be present in sufficient amounts of oxygen atoms to oxidize the transition metal.

[0258] When the oxidizing atmosphere is an oxygen-containing atmosphere, the atmosphere in the reaction vessel can be controlled by a method such as passing an oxidizing gas through the reaction vessel or bubbling an oxidizing gas in the mixed liquid.

[0259] After the above reaction, the obtained reaction precipitate is washed with water and then dried to obtain a metal composite compound. In the present embodiment, nickel-cobalt-manganese hydroxide is obtained as the metal composite compound.

[0260] In addition, when impurities from the mixed solution remain in the reaction precipitate when washed with water alone, the reaction precipitate may be washed with weak acid water or an alkaline solution as needed. Examples of the alkaline solution include aqueous solutions containing sodium hydroxide or potassium hydroxide.

[0261] By applying an appropriate external force to the metal composite compound obtained by drying to pulverize it and adjust the dispersion state of the particles, it is possible to obtain a metal composite hydroxide that is easy to obtain a positive electrode active material that satisfies the above-mentioned (Requirement 2).

[0262] "Appropriate external force" refers to an external force that does not destroy the crystallites of the metal composite compound and disperses the agglomerated state. In the above-mentioned pulverization, a grinder is preferably used as a pulverizer, and a stone mill grinder is particularly preferred. When a stone mill grinder is used, the interval between the upper grind and the lower grind is preferably adjusted according to the agglomerated state of the metal composite hydroxide. The interval between the upper grind and the lower grind is preferably in the range of 10 μm to 200 μm, for example.

[0263] Furthermore, in the above examples, a nickel-cobalt-manganese composite hydroxide was produced, but a nickel-cobalt-manganese composite oxide may also be produced.

[0264] The nickel-cobalt-manganese composite oxide can be prepared by oxidizing the nickel-cobalt-manganese composite hydroxide.

[0265] (Process for producing lithium metal composite oxide)

[0266] In this step, after the metal composite oxide or metal composite hydroxide is dried, the metal composite oxide or metal composite hydroxide is mixed with a lithium compound.

[0267] When the metal composite oxide or metal composite hydroxide and the lithium compound are mixed, it is preferred that an inert flux is mixed simultaneously.

[0268] By firing a mixture containing a metal composite oxide, a lithium compound and an inactive flux, or a mixture containing a metal composite hydroxide, a lithium compound and an inactive flux, the mixture of the metal composite compound and the lithium compound is fired in the presence of an inactive flux.

[0269] By firing the mixture of the metal composite compound and the lithium compound in the presence of an inactive flux, it is difficult to generate secondary particles formed by sintering primary particles together. In addition, the growth of single particles can be promoted.

[0270] As the lithium compound, any one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide, lithium oxide, lithium chloride, and lithium fluoride can be used, or two or more thereof can be mixed and used. Among them, any one or both of lithium hydroxide and lithium carbonate are preferred.

[0271] When the lithium hydroxide contains lithium carbonate as an impurity, the content of lithium carbonate in the lithium hydroxide is preferably 5% by mass or less.

[0272] The lithium compound is preferably crushed before mixing with the metal composite oxide. For example, coarse particles in the lithium compound powder as a raw material will hinder the growth of the lithium metal composite oxide particles. Here, "coarse particles" refer to particles with a particle size of 200 μm or more, for example.

[0273] When the lithium compound is pulverized and micronized before mixing with the metal composite oxide, the particles of the lithium metal composite oxide grow easily, and a positive electrode active material satisfying all of the above formulae (1) to (3) can be easily obtained.

[0274] There is no particular limitation on the method for pulverizing, and a known method can be appropriately used. For example, a mortar, a ball mill, a planetary ball mill, a dynamic mill, a bead mill, a jet mill, a hammer mill, a disc mill, a pin mill, etc. can be used. Among them, a dynamic mill is preferred.

[0275] The screw rotation speed of the pulverizer when pulverizing the lithium compound may be appropriately adjusted within the range of 500 rpm to 2000 rpm.

[0276] When the lithium compound is pulverized, the amount of the lithium compound supplied to the pulverizer may be appropriately adjusted within a range of 10 kg / hour to 20 kg / hour.

[0277] When the lithium compound is pulverized, it is preferred that the lithium compound be pulverized until the maximum particle size becomes 100 μm or less.

[0278] The drying conditions of the metal composite oxide or metal composite hydroxide are not particularly limited, and the drying conditions may be, for example, any one of the following conditions 1) to 3).

[0279] 1) Conditions under which the metal composite oxide or metal composite hydroxide is not oxidized or reduced. Specifically, conditions under which the oxide remains in an oxide state, and conditions under which the hydroxide remains in a hydroxide state.

[0280] 2) Conditions for oxidation of metal composite hydroxides: Specifically, dry conditions for oxidation of hydroxides to oxides.

[0281] 3) Conditions under which the metal composite oxide is reduced. Specifically, dry conditions under which the oxide is reduced to a hydroxide.

[0282] In order to achieve a condition where the material is not oxidized or reduced, an inert gas such as nitrogen, helium, or argon may be used as the atmosphere during drying.

[0283] In order to achieve the condition where the hydroxide is oxidized, oxygen or air may be used as the atmosphere during drying.

[0284] In order to achieve conditions under which the metal composite oxide is reduced, it is sufficient to use a reducing agent such as hydrazine or sodium sulfite under an inert gas atmosphere during drying.

[0285] After the metal composite oxide or metal composite hydroxide is dried, it may be appropriately classified.

[0286] The above lithium compounds and metal composite compounds are used in consideration of the composition ratio of the final target. For example, when a nickel-cobalt-manganese composite compound is used, the lithium compound and the metal composite compound are used in an amount corresponding to Li[Li x (Ni (1-y-z) Co y Mn z ) 1-x ]The ratio of the composition ratio of O2 is used.

[0287] When Li is excessive (containing a molar ratio exceeding 1) in the final target lithium metal composite oxide, the lithium compound and the metal element contained in the metal composite compound are mixed in a ratio exceeding 1 in molar ratio.

[0288] The lithium-nickel-cobalt-manganese composite oxide can be obtained by firing a mixture of the nickel-cobalt-manganese composite compound and the lithium compound. In addition, the firing may be performed using dry air, oxygen atmosphere, inert atmosphere, etc. depending on the desired composition, and multiple firing steps may be performed if necessary.

[0289] In this embodiment, the mixture may be fired in the presence of an inactive flux. By firing in the presence of an inactive flux, the reaction of the mixture may be promoted. The inactive flux may remain in the fired lithium metal composite oxide, or may be removed by washing with water or alcohol after firing.

[0290] By adjusting the holding temperature of the sintering, the particle size of the single particle can be controlled within the preferred range of this embodiment.

[0291] The firing step may be a single firing step or may include a plurality of firing steps.

[0292] When there are multiple firing stages, the process of firing at the highest temperature is recorded as the main firing. Before the main firing, a temporary firing at a temperature lower than the main firing may be performed. In addition, after the main firing, a post-firing at a temperature lower than the main firing may be performed.

[0293] The firing temperature (maximum holding temperature) of the main firing is preferably 600° C. or higher, more preferably 700° C. or higher, and particularly preferably 800° C. or higher from the viewpoint of promoting particle growth. In addition, from the viewpoint of preventing particle fracture and maintaining particle strength, it is preferably 1200° C. or lower, more preferably 1100° C. or lower, and particularly preferably 1000° C. or lower.

[0294] The upper limit value and the lower limit value of the maximum holding temperature of the main firing can be arbitrarily combined.

[0295] Examples of the combination include 600°C to 1200°C, 700°C to 1100°C, and 800°C to 1000°C.

[0296] The firing temperature of the temporary firing or the post-firing may be lower than the firing temperature of the main firing, and may be, for example, in the range of 350°C to 700°C.

[0297] Generally, the higher the holding temperature, the larger the particle size of the single particle and the smaller the BET specific surface area. The holding temperature during firing can be appropriately adjusted according to the type and amount of the transition metal element, precipitant, and inactive flux used.

[0298] The holding temperature may be set in consideration of the melting point of the inert flux described below, and is preferably set within a range of the melting point of the inert flux - 200°C to the melting point of the inert flux + 200°C.

[0299] In addition, the time for holding at the holding temperature can be 0.1 hour to 20 hours, preferably 0.5 hour to 10 hours. The heating rate to the holding temperature is usually 50°C / hour to 400°C / hour, and the cooling rate from the holding temperature to room temperature is usually 10°C / hour to 400°C / hour. In addition, as the sintering atmosphere, air, oxygen, nitrogen, argon or a mixed gas thereof can be used.

[0300] The lithium metal composite oxide obtained by calcining is crushed and appropriately classified to become a positive electrode active material that can be applied to all-solid lithium ion batteries.

[0301] In the present embodiment, the lithium metal composite oxide obtained by firing is pulverized by applying an appropriate external force and adjusting the dispersion state of the particles, thereby obtaining a positive electrode active material satisfying the above-mentioned (Requirement 2).

[0302] "Appropriate external force" refers to an external force of a degree that does not destroy the crystallites of the lithium metal composite oxide and disperses the agglomerated state. When pulverizing, a grinder is preferably used as a grinder, and a stone mill grinder is particularly preferred. When a stone mill grinder is used, the interval between the upper grind and the lower grind is preferably adjusted according to the agglomerated state of the lithium metal composite oxide. The interval between the upper grind and the lower grind is preferably in the range of 10 μm to 200 μm, for example.

[0303] The inactive flux is not particularly limited as long as it is not easy to react with the mixture during firing. In the present embodiment, the inactive flux may include fluorides of one or more elements (hereinafter referred to as "A") selected from Na, K, Rb, Cs, Ca, Mg, Sr and Ba, chlorides of A, carbonates of A, sulfates of A, nitrates of A, phosphates of A, hydroxides of A, molybdates of A and tungstates of A.

[0304] As fluorides of A, there are NaF (melting point: 993°C), KF (melting point: 858°C), RbF (melting point: 795°C), CsF (melting point: 682°C), CaF2 (melting point: 1402°C), MgF2 (melting point: 1263°C), SrF2 (melting point: 1473°C) and BaF2 (melting point: 1355°C).

[0305] As chlorides of A, there can be mentioned NaCl (melting point: 801°C), KCl (melting point: 770°C), RbCl (melting point: 718°C), CsCl (melting point: 645°C), CaCl2 (melting point: 782°C), MgCl2 (melting point: 714°C), SrCl2 (melting point: 857°C) and BaCl2 (melting point: 963°C).

[0306] As carbonates of A, there are Na2CO3 (melting point: 854°C), K2CO3 (melting point: 899°C), Rb2CO3 (melting point: 837°C), Cs2CO3 (melting point: 793°C), CaCO3 (melting point: 825°C), MgCO3 (melting point: 990°C), SrCO3 (melting point: 1497°C) and BaCO3 (melting point: 1380°C).

[0307] As sulfates of A, there are Na2SO4 (melting point: 884°C), K2SO4 (melting point: 1069°C), Rb2SO4 (melting point: 1066°C), Cs2SO4 (melting point: 1005°C), CaSO4 (melting point: 1460°C), MgSO4 (melting point: 1137°C), SrSO4 (melting point: 1605°C) and BaSO4 (melting point: 1580°C).

[0308] Examples of the nitrate of A, the phosphate of A, the hydroxide of A, the molybdate of A, and the tungstate of A include compounds described in JP6734491B.

[0309] In the present embodiment, two or more of these inert fluxes may be used. When two or more of these inert fluxes are used, the melting point of the entire inert flux may decrease.

[0310] Among these inert fluxes, one or more salts selected from the group consisting of A carbonates, A sulfates, and A chlorides are preferred as an inert flux for obtaining a lithium metal composite oxide having higher crystallinity.

[0311] In addition, A is preferably any one or both of Na and K.

[0312] That is, among the above-mentioned inert fluxes, a particularly preferred inert flux is preferably one or more selected from NaCl, KCl, Na2CO3, K2CO3, Na2SO4 and K2SO4, and more preferably any one or both of K2SO4 and Na2SO4 are used.

[0313] In the present embodiment, the amount of the inactive flux present during firing may be appropriately selected. For example, the amount of the inactive flux present during firing is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the lithium compound.

[0314] In order to further promote the growth of crystals, an inactive flux other than the above-mentioned inactive flux may be used in combination. Examples of the inactive flux used in this case include ammonium salts such as NH4Cl and NH4F.

[0315] (Coating layer formation step)

[0316] When forming a coating layer on the surface of a lithium metal composite oxide, first, a coating material raw material and a lithium metal composite oxide are mixed, and then, if necessary, heat treatment is performed to form a coating layer on the surface of the lithium metal composite oxide particles.

[0317] Depending on the type of the coating material raw material, in the above-mentioned lithium metal composite oxide production step, when the metal composite compound and the lithium compound are mixed, the coating material raw material may be further added and mixed.

[0318] As the method for forming the coating layer or the coating material raw material of the present embodiment, the method or the coating material raw material described in JP6734491B can be applied.

[0319] When a compound containing Al is used as the coating material raw material, it is preferably fired at a temperature range of 600°C to 800°C for 4 to 10 hours. By firing at such a high temperature and long time, a positive electrode active material satisfying (Requirement 2) can be easily obtained.

[0320] The particles having the coating layer formed on the surface of the primary particles or secondary particles of the lithium metal composite oxide are appropriately pulverized and classified to obtain a positive electrode active material.

[0321] <Method 2 for producing positive electrode active material>

[0322] When the positive electrode active material includes single particles and secondary particles, the positive electrode active material can be produced by performing the following changes to the above-mentioned method 1 for producing the positive electrode active material.

[0323] (Metal Composite Compound Manufacturing Process)

[0324] In the second method for producing a positive electrode active material, in the step of producing a metal composite compound, a metal composite compound that eventually forms single particles and a metal composite compound that forms secondary particles are produced separately.

[0325] Hereinafter, a metal composite compound that eventually forms a single particle may be referred to as a “single particle precursor.” Also, a metal composite compound that eventually forms a secondary particle may be referred to as a “secondary particle precursor.”

[0326] In the second method for producing a positive electrode active material, when producing a metal composite compound by the above-mentioned coprecipitation method, a first coprecipitation tank for producing a single particle precursor and a second coprecipitation tank for forming a secondary particle precursor are used.

[0327] By appropriately controlling the concentration of the metal salt supplied to the first coprecipitation tank, the stirring speed, the reaction temperature, the reaction pH, the calcination conditions described below, and the like, a single particle precursor can be produced.

[0328] Specifically, the temperature of the reaction tank is preferably controlled within a range of, for example, 30°C to 80°C, more preferably 40°C to 70°C. For the second reaction tank described below, the range is more preferably ±20°C.

[0329] The pH value in the reaction tank is preferably controlled within the range of pH 10 to pH 13, more preferably pH 11 to pH 12.5. In addition, the pH value in the second reaction tank described below is more preferably within the range of ±pH 2, and particularly preferably a higher pH than that in the second reaction tank.

[0330] In addition, by appropriately controlling the concentration of the metal salt supplied to the second coprecipitation tank, the stirring speed, the reaction temperature, the reaction pH, the calcination conditions described below, and the like, a secondary particle precursor can be produced.

[0331] Specifically, the temperature of the reaction tank is preferably controlled within a range of, for example, 20°C to 80°C, more preferably 30°C to 70°C. For the second reaction tank described below, the range is more preferably ±20°C.

[0332] The pH value in the reaction tank is preferably controlled within the range of pH 10 to pH 13, more preferably pH 11 to pH 12.5. For the second reaction tank described below, the pH is more preferably within the range of ±pH 2, and particularly preferably lower than that of the second reaction tank.

[0333] The reaction products thus obtained were washed with water and then dried to separate the nickel-cobalt-manganese composite hydroxide. The separated nickel-cobalt-manganese composite hydroxide contained a single particle precursor and a secondary particle precursor.

[0334] In the above example, a nickel-cobalt-manganese composite hydroxide is produced, but a nickel-cobalt-manganese composite oxide can also be produced. For example, a nickel-cobalt-manganese composite oxide can be produced by oxidizing a nickel-cobalt-manganese composite hydroxide.

[0335] (Process for producing lithium metal composite oxide)

[0336] In the production process of lithium metal composite oxide, the single particle precursor obtained in the above process and the metal composite oxide or metal composite hydroxide as a secondary particle precursor are dried and then mixed with a lithium compound. The single particle precursor and the secondary particle precursor may be appropriately classified after drying.

[0337] By mixing the single particle precursor and the secondary particle precursor at a predetermined mass ratio during mixing, the abundance ratio of the single particles to the secondary particles in the obtained positive electrode active material can be roughly controlled.

[0338] In the step after mixing, the single particle precursor and the secondary particle precursor may be aggregated or separated, and the secondary particles generated by the aggregation of the single particle precursor and the single particles generated by the separation of the secondary particle precursor may exist separately.

[0339] By adjusting the mixing ratio of the single particle precursor and the secondary particle precursor and the conditions of the steps after mixing, the abundance ratio of the single particles and the secondary particles in the finally obtained positive electrode active material can be controlled.

[0340] By adjusting the holding temperature during firing, the average particle size of the single particles and the average particle size of the secondary particles of the obtained lithium metal composite oxide can be controlled within the preferred range of the present embodiment.

[0341] <Method for producing positive electrode active material 3>

[0342] In addition, when the positive electrode active material includes single particles and secondary particles, the first lithium metal composite oxide composed of single particles and the second lithium metal composite oxide composed of secondary particles can be manufactured separately by the above-mentioned positive electrode active material manufacturing method 1, and the first lithium metal composite oxide and the second lithium metal composite oxide can be mixed to thereby manufacture.

[0343] In the manufacturing method 3 of the positive electrode active material, in the manufacturing process of the lithium metal composite oxide, the holding temperature when the first lithium metal composite oxide is fired can be higher than the holding temperature when the second lithium metal composite oxide is fired. Specifically, when the first lithium metal composite oxide is manufactured, the holding temperature is preferably 30° C. or more higher, more preferably 50° C. or more higher, and further preferably 80° C. or more higher than the holding temperature of the second lithium metal composite oxide.

[0344] By mixing the obtained first lithium metal composite oxide and second lithium metal composite oxide at a predetermined ratio, a positive electrode active material including single particles and secondary particles can be obtained.

[0345] <All-solid-state lithium-ion battery>

[0346] Next, the structure of the all-solid lithium ion battery is described, and a positive electrode using the all-solid lithium ion battery positive electrode active material of one embodiment of the present invention as the positive electrode active material of the all-solid lithium ion battery and an all-solid lithium ion battery having the positive electrode are described. The all-solid lithium ion battery of this embodiment is a secondary battery.

[0347] Figure 1 , 2 It is a schematic diagram showing an example of the all-solid-state lithium ion battery according to the present embodiment. Figure 1 Schematic diagram showing a stacked body included in the all-solid-state lithium ion battery of the present embodiment. Figure 2 It is a schematic diagram showing the overall structure of the all-solid-state lithium ion battery according to the present embodiment.

[0348] The all-solid lithium ion battery 1000 includes a stacked body 100 including a positive electrode 110 , a negative electrode 120 , and a solid electrolyte layer 130 , and an outer casing 200 that accommodates the stacked body 100 .

[0349] The materials constituting each member will be described later.

[0350] The laminate 100 may include an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122 .

[0351] In the stack 100, the positive electrode 110 and the negative electrode 120 sandwich the solid electrolyte layer 130 in a manner that does not short-circuit each other. In addition, the all-solid lithium ion battery 1000 may also have a separator used in a conventional liquid lithium ion secondary battery between the positive electrode 110 and the negative electrode 120 to prevent the positive electrode 110 and the negative electrode 120 from short-circuiting.

[0352] The all-solid lithium ion battery 1000 includes an insulator (not shown) that insulates the stacked body 100 from the outer casing 200 , or a sealing body (not shown) that seals the opening 200 a of the outer casing 200 .

[0353] The outer package 200 may be formed of a metal material having high corrosion resistance, such as aluminum, stainless steel, or nickel-plated steel. Alternatively, a container formed of a laminate film having at least one surface subjected to corrosion resistance treatment and processed into a bag shape may be used.

[0354] Examples of the shape of the all-solid lithium ion battery 1000 include a coin shape, a button shape, a paper shape (or a sheet shape), a cylindrical shape, and a square shape.

[0355] The all-solid lithium ion battery 1000 is shown as having one stack 100 , but is not limited thereto. The all-solid lithium ion battery 1000 may also be configured such that the stack 100 is used as a unit element and a plurality of unit elements (stacks 100 ) are sealed inside an outer package 200 .

[0356] Hereinafter, each configuration will be described in sequence.

[0357] (positive electrode)

[0358] The positive electrode 110 includes a positive electrode active material layer 111 and a positive electrode current collector 112 .

[0359] The positive electrode active material layer 111 contains the positive electrode active material which is one embodiment of the present invention described above. In addition, the positive electrode active material layer 111 may further contain a solid electrolyte (second solid electrolyte), a conductive material, and a binder.

[0360] The positive electrode active material contained in the positive electrode active material layer 111 is in contact with the solid electrolyte contained in the positive electrode active material layer 111. In detail, the positive electrode active material layer 111 includes a plurality of particles (positive electrode active material) of a lithium metal composite oxide crystal and a solid electrolyte in contact with particles (positive electrode active material) filled between the plurality of particles (positive electrode active material).

[0361] (Solid Electrolyte)

[0362] As the solid electrolyte that the positive electrode active material layer 111 can have, a solid electrolyte having lithium ion conductivity and used in a known all-solid-state battery can be adopted. As such a solid electrolyte, an inorganic electrolyte and an organic electrolyte can be cited. As the inorganic electrolyte, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, and a hydride-based solid electrolyte can be cited. As the organic electrolyte, a polymer-based solid electrolyte can be cited.

[0363] In the present embodiment, the solid electrolyte is preferably an oxide-based solid electrolyte or a sulfide-based solid electrolyte, and more preferably an oxide-based solid electrolyte.

[0364] (Oxide-based solid electrolyte)

[0365] As the oxide-based solid electrolyte, for example, perovskite-type oxides, NASICON-type oxides, LISICON-type oxides, garnet-type oxides, etc. can be cited.

[0366] As the perovskite-type oxide, Li a La 1-a TiO3 (0 < a < 1) and other Li-La-Ti-based oxides, Li b La 1- b TaO3 (0 < b < 1) and other Li-La-Ta-based oxides, Li c La 1-c NbO3 (0 < c < 1) and other Li-La-Nb-based oxides, etc.

[0367] As the NASICON-type oxide, Li 1+d Al d Ti 2-d (PO4)3 (0 ≤ d ≤ 1), etc. The NASICON-type oxide is an oxide represented by Li m M 1 n M 2 o P p O q .

[0368] In the formula, M 1 is one or more elements selected from B, Al, Ga, In, C, Si, Ge, Sn, Sb, and Se.

[0369] In the formula, M 2 is one or more elements selected from Ti, Zr, Ge, In, Ga, Sn, and Al.

[0370] In the formula, m, n, o, p, and q are arbitrary positive numbers.

[0371] Examples of LISICON type oxides include Li4M 3 O4-Li3M 4 Oxide represented by O4, etc.

[0372] Where M 3 It is one or more elements selected from Si, Ge and Ti.

[0373] Where M 4 It is one or more elements selected from P, As and V.

[0374] As garnet-type oxides, Li7La3Zr2O 12 (LLZ) and other Li-La-Zr oxides.

[0375] The oxide-based solid electrolyte may be a crystalline material or an amorphous material. Examples of amorphous solid electrolytes include Li-BO compounds such as Li3BO3, Li2B4O7, and LiBO2. The oxide-based solid electrolyte preferably includes an amorphous material.

[0376] (Sulfide-based solid electrolyte)

[0377] Examples of sulfide-based solid electrolytes include Li2S-P2S5 compounds, Li2S-SiS2 compounds, Li2S-GeS2 compounds, Li2S-B2S3 compounds, Li2S-P2S3 compounds, LiI-Si2S-P2S5 compounds, LiI-Li2S-P2O5 compounds, LiI-Li3PO4-P2S5 compounds, Li 10 GeP2S 12 wait.

[0378] In addition, in this specification, the expression "system compound" referring to the sulfide-based solid electrolyte is used as a general term for solid electrolytes mainly including raw materials such as "Li2S" and "P2S5" described before the "system compound". For example, the Li2S-P2S5 system compound includes a solid electrolyte containing Li2S and P2S5, and further containing other raw materials. In addition, the Li2S-P2S5 system compound also includes a solid electrolyte in which the mixing ratio of Li2S and P2S5 is different.

[0379] Examples of Li2S-P2S5 compounds include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-Z m Sn (m and n are positive numbers. Z is Ge, Zn or Ga), etc.

[0380] Examples of Li2S-SiS2 compounds include Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li2SO4, Li2S-SiS2-Li x MO y (x and y are positive numbers. M is P, Si, Ge, B, Al, Ga or In), etc.

[0381] Examples of Li2S-GeS2 compounds include Li2S-GeS2, Li2S-GeS2-P2S5, and the like.

[0382] The sulfide-based solid electrolyte may be a crystalline material or an amorphous (amorphous) material. The sulfide-based solid electrolyte preferably includes an amorphous material.

[0383] (Hydride-based solid electrolyte)

[0384] As hydride-based solid electrolyte materials, there can be mentioned LiBH4, LiBH4-3KI, LiBH4-PI2, LiBH4-P2S5, LiBH4-LiNH2, 3LiBH4-LiI, LiNH2, Li2AlH6, Li(NH2)2I, Li2NH, LiGd(BH4)3Cl, Li2(BH4)(NH2), Li3(NH2)I, Li4(BH4)(NH2)3, etc.

[0385] Examples of the polymer solid electrolyte include organic polymer electrolytes including one or more polymer compounds selected from polyethylene oxide polymer compounds, polysiloxane chains, and polyoxyalkylene chains.

[0386] Two or more solid electrolytes may be used in combination within a range not impairing the effects of the invention.

[0387] (Conductive materials)

[0388] As the conductive material that the positive electrode active material layer 111 may also have, a carbon material or a metal compound may be used. As the carbon material, graphite powder, carbon black (e.g., acetylene black), fibrous carbon material, etc. may be cited. Since carbon black is a particle with a large surface area, by adding an appropriate amount to the positive electrode active material layer 111, the conductivity inside the positive electrode 110, the charging efficiency, the discharging efficiency, and the output power characteristics can be improved.

[0389] On the other hand, when the amount of carbon black added is too large, the binding force between the positive electrode active material layer 111 and the positive electrode current collector 112 and the binding force inside the positive electrode active material layer 111 are reduced, and the internal resistance is increased.

[0390] Examples of the metal compound include conductive metals, metal alloys, and metal oxides.

[0391] The proportion of the conductive material in the positive electrode active material layer 111 is preferably 5 to 20 parts by mass relative to 100 parts by mass of the positive electrode active material when the conductive material is a carbon material. When a fibrous carbon material such as graphitized carbon fiber or carbon nanotube is used as the conductive material, the proportion may be reduced.

[0392] (Adhesive)

[0393] When the positive electrode active material layer 111 has a binder, a thermoplastic resin can be used as the binder. Examples of the thermoplastic resin include polyimide resins, fluorine-containing resins, polyolefin resins, and ethyl cellulose.

[0394] Examples of the fluorine-containing resin include polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers.

[0395] Hereinafter, polyvinylidene fluoride may be referred to as PVdF. Also, polytetrafluoroethylene may be referred to as PTFE.

[0396] Examples of the polyolefin resin include polyethylene and polypropylene.

[0397] These thermoplastic resins may be mixed and used in two or more kinds. When a fluorine-containing resin and a polyolefin resin are used as a binder, for example, the ratio of the fluorine-containing resin to the entire positive electrode active material layer 111 is 1% to 10% by mass, and the ratio of the polyolefin resin is 0.1% to 2% by mass. At this time, the positive electrode active material layer 111 has a high adhesion force between the positive electrode active material layer 111 and the positive electrode collector 112 and a high bonding force inside the positive electrode active material layer 111.

[0398] The positive electrode active material layer 111 may be processed in advance as a thin sheet-shaped body containing a positive electrode active material and used as an "electrode" in the present invention. In addition, in the following description, such a thin sheet-shaped body is sometimes referred to as a "positive electrode active material sheet". A laminated body in which a current collector is laminated on a positive electrode active material sheet may also be used as an electrode.

[0399] The positive electrode active material sheet may further include any one or more selected from the above-mentioned solid electrolyte, conductive material and binder.

[0400] The positive electrode active material sheet is obtained by, for example, mixing the positive electrode active material, the sintering aid, the above conductive material, the above binder, a plasticizer, and a solvent to prepare a slurry, applying the obtained slurry on a carrier film, and drying the mixture.

[0401] As a sintering aid, for example, Li 3 BO 3 or Al 2 O 3 can be used.

[0402] As the plasticizer, for example, dioctyl phthalate can be used.

[0403] As the solvent, for example, acetone, ethanol, or N-methyl-2-pyrrolidone can be used.

[0404] When preparing the slurry, a ball mill can be used for mixing. Since the obtained mixture contains many bubbles mixed in during mixing, it can also be decompressed and degassed. When degassed, a part of the solvent is volatilized and concentrated, and the slurry is made more viscous.

[0405] The slurry can be applied using a known doctor blade.

[0406] A PET film can be used as the carrier film.

[0407] The positive electrode active material sheet obtained after drying is peeled off from the carrier film and processed into a necessary shape by punching as appropriate before use. In addition, the positive electrode active material sheet can also be subjected to uniaxial pressing in the thickness direction as appropriate.

[0408] (Positive electrode collector)

[0409] The positive electrode current collector 112 of the positive electrode 110 may be a sheet-like member formed of a metal material such as Al, Ni, stainless steel, or Au. Of these, it is preferred to use Al as the forming material and process it into a thin film because it is easy to process and inexpensive.

[0410] As a method for supporting the positive electrode active material layer 111 on the positive electrode current collector 112, there is a method of press-molding the positive electrode active material layer 111 on the positive electrode current collector 112. For press-molding, cold pressing or hot pressing can be used.

[0411] In addition, an organic solvent is used to make a mixture of a positive electrode active material, a solid electrolyte, a conductive material, and a binder into a paste to form a positive electrode mixture, and the obtained positive electrode mixture is applied to at least one side of the positive electrode collector 112, dried, pressed, and fixed, so that the positive electrode active material layer 111 can be supported on the positive electrode collector 112.

[0412] In addition, an organic solvent is used to make a mixture of a positive electrode active material, a solid electrolyte, and a conductive material into a paste to form a positive electrode mixture, and the obtained positive electrode mixture is applied to at least one side of the positive electrode collector 112, dried, and sintered, so that the positive electrode active material layer 111 can be supported on the positive electrode collector 112.

[0413] Examples of the organic solvent that can be used in the positive electrode mixture include amine solvents, ether solvents, ketone solvents, ester solvents, and amide solvents.

[0414] Examples of the amine solvent include N,N-dimethylaminopropylamine and diethylenetriamine.

[0415] Examples of the ether solvent include tetrahydrofuran.

[0416] Examples of the ketone solvent include methyl ethyl ketone.

[0417] Examples of the ester solvent include methyl acetate.

[0418] Examples of the amide solvent include dimethylacetamide and N-methyl-2-pyrrolidone. Hereinafter, N-methyl-2-pyrrolidone may be referred to as NMP.

[0419] Examples of a method for coating the positive electrode mixture on the positive electrode current collector 112 include a slit coating method, a screen coating method, a curtain coating method, a doctor blade coating method, a gravure coating method, and an electrostatic spray method.

[0420] The positive electrode 110 can be manufactured by the above-listed methods.

[0421] (negative electrode)

[0422] The negative electrode 120 includes a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 includes a negative electrode active material. In addition, the negative electrode active material layer 121 may further include a solid electrolyte and a conductive material. The solid electrolyte, conductive material, and binder may be the above-mentioned substances.

[0423] (Negative electrode active material)

[0424] Examples of the negative electrode active material in the negative electrode active material layer 121 include carbon materials, chalcogenides (oxides, sulfides, etc.), nitrides, metals, or alloys, and materials that can be doped and dedoped with lithium ions at a potential lower than that of the positive electrode 110 .

[0425] Carbon materials that can be used as the negative electrode active material include graphites such as natural graphite and artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fibers, and organic polymer compound fired products.

[0426] Oxides that can be used as the negative electrode active material include the following.

[0427] ·SiO2, SiO, etc. are used in the formula SiO x (here, x is a positive real number) represents silicon oxide.

[0428] ·TiO2, TiO, etc. are used in the formula TiO x (here, x is a positive real number) is an oxide of titanium represented by.

[0429] ·V2O5, VO2, etc. use the formula VO x (here, x is a positive real number) represents an oxide of vanadium.

[0430] ·Fe3O4, Fe2O3, FeO, etc. are used in the formula FeO x (here, x is a positive real number) represents an iron oxide.

[0431] ·SnO2, SnO, etc. are used as SnO x (here, x is a positive real number) represents tin oxide.

[0432] WO3, WO2, etc. use the general formula WO x (here, x is a positive real number) represents tungsten oxide.

[0433] ·Li4Ti5O 12 , LiVO2 and other metal composite oxides containing lithium, titanium or vanadium.

[0434] Sulfides that can be used as the negative electrode active material include the following.

[0435] ·Ti2S3, TiS2, TiS etc. are used in the formula TiS x (here, x is a positive real number) represents titanium sulfide.

[0436] ·VS for V3S4, VS2, VS, etc. x (here, x is a positive real number) represents a vanadium sulfide.

[0437] ·Fe3S4, FeS2, FeS etc. x (here, x is a positive real number) represents iron sulfide.

[0438] ·Mo2S3, MoS2, etc. x (here, x is a positive real number) represents a molybdenum sulfide.

[0439] SnS2, SnS, etc. x (here, x is a positive real number) represents a tin sulfide.

[0440] · Tungsten sulfides represented by WS x (where x is a positive real number).

[0441] · Antimony sulfides represented by SbS x (where x is a positive real number).

[0442] · Selenium sulfides represented by SeS such as Se5S3, SeS2, SeS x (where x is a positive real number).

[0443] As nitrides that can be used as negative electrode active materials, Li3N, Li 3-x A x N (where A is either or both of Ni and Co, 0 < x < 3) and other lithium-containing nitrides can be mentioned.

[0444] These carbon materials, oxides, sulfides, and nitrides can be used alone or in combination of two or more. In addition, these carbon materials, oxides, sulfides, and nitrides can be either crystalline or amorphous.

[0445] In addition, as metals that can be used as negative electrode active materials, lithium metal, silicon metal, tin metal, etc. can be mentioned.

[0446] As alloys that can be used as negative electrode active materials, lithium alloys, silicon alloys, tin alloys, Cu2Sb, La3Ni2Sn7, etc. can also be mentioned.

[0447] As lithium alloys, Li-Al, Li-Ni, Li-Si, Li-Sn, Li-Sn-Ni, etc. can be mentioned.

[0448] As silicon alloys, Si-Zn can be mentioned.

[0449] As tin alloys, Sn-Mn, Sn-Co, Sn-Ni, Sn-Cu, Sn-La, etc. can be mentioned.

[0450] These metals or alloys are mainly used as electrodes alone after being processed into foil shape, for example.

[0451] Among the above-mentioned negative electrode active materials, carbon materials mainly composed of graphite such as natural graphite and artificial graphite are preferably used. The reason is that during charging, from the uncharged state to the fully charged state, the potential of the negative electrode 120 hardly changes (good potential flatness), the average discharge potential is low, and the capacity retention rate during repeated charge and discharge is high (good cycle characteristics), etc.

[0452] As the shape of the carbon material, for example, it can be any one of flaky like natural graphite, spherical like mesophase carbon microspheres, fibrous like graphitized carbon fibers, or aggregates of micro-powders, etc.

[0453] Among the negative electrode active materials, oxides are preferably used because they have high thermal stability and are less likely to generate dendrites (dendrites) due to Li metal. As the shape of the oxide, fibers or agglomerates of fine powders are preferably used.

[0454] (Negative electrode current collector)

[0455] The negative electrode current collector 122 of the negative electrode 120 may be a strip-shaped member formed of a metal material such as Cu, Ni, or stainless steel. Of these, Cu is preferably formed into a thin film because it is difficult to alloy with lithium and can be easily processed.

[0456] As a method for making the negative electrode active material layer 121 be carried on the negative electrode collector 122, similar to the case of the positive electrode 110, there can be cited a method of utilizing pressure molding; a method of applying a paste of negative electrode mixture containing negative electrode active material on the negative electrode collector 122, and pressing and strongly bonding the mixture after drying; and a method of applying a paste of negative electrode mixture containing negative electrode active material on the negative electrode collector 122, and sintering the mixture after drying.

[0457] (Solid Electrolyte Layer)

[0458] The solid electrolyte layer 130 includes the above-mentioned solid electrolyte (first solid electrolyte). When the positive electrode active material layer 111 includes a solid electrolyte, the solid electrolyte (first solid electrolyte) constituting the solid electrolyte layer 130 and the solid electrolyte (second solid electrolyte) included in the positive electrode active material layer 111 may be the same substance. The solid electrolyte layer 130 functions as a medium for transferring lithium ions and also functions as a separator for separating the positive electrode 110 and the negative electrode 120.

[0459] The solid electrolyte layer 130 may be formed by depositing an inorganic solid electrolyte on the surface of the positive electrode active material layer 111 of the positive electrode 110 using a sputtering method.

[0460] In addition, the solid electrolyte layer 130 can be formed by applying a paste mixture containing a solid electrolyte on the surface of the positive electrode active material layer 111 of the positive electrode 110 and drying it. After drying, the solid electrolyte layer 130 can also be formed by pressurizing and then pressing by cold isostatic pressing (CIP).

[0461] Furthermore, the solid electrolyte layer 130 may be formed by forming a solid electrolyte into particles in advance, overlapping the solid electrolyte particles with the positive electrode active material sheet, and uniaxially pressing them in the stacking direction. The positive electrode active material sheet becomes the positive electrode active material layer 111 .

[0462] The positive electrode current collector 112 is further disposed on the positive electrode active material layer 111 for the obtained stack of the positive electrode active material layer 111 and the solid electrolyte layer 130. The solid electrolyte layer 130 and the positive electrode 110 can be formed by uniaxial pressing in the stacking direction and sintering.

[0463] Such positive electrode 110 is in contact with solid electrolyte layer 130. Solid electrolyte layer 130 includes a first solid electrolyte.

[0464] The positive electrode 110 has a positive electrode active material layer 111 in contact with the solid electrolyte layer 130 and a positive electrode current collector 112 stacked with the positive electrode active material layer 111. The positive electrode active material layer 111 includes a plurality of particles of crystals containing a lithium metal composite oxide (i.e., a positive electrode active material as one embodiment of the present invention) and a solid electrolyte (a second solid electrolyte) filled between the plurality of particles and in contact with the particles.

[0465] The solid electrolyte and particles included in the positive electrode active material layer 111 are in contact with the solid electrolyte layer 130 . That is, the particles included in the positive electrode active material layer 111 are in contact with the solid electrolyte included in the positive electrode active material layer 111 and the solid electrolyte layer 130 .

[0466] It is not necessary for all particles (positive electrode active material) contained in the positive electrode active material layer 111 to be in contact with the solid electrolyte contained in the positive electrode active material layer 111 and the solid electrolyte layer 130 .

[0467] The positive electrode active material contained in the positive electrode active material layer 111 is in contact with the solid electrolyte contained in the positive electrode active material layer 111, and is electrically connected to the solid electrolyte contained in the positive electrode active material layer 111. In addition, the positive electrode active material contained in the positive electrode active material layer 111 is in contact with the solid electrolyte layer 130, and is electrically connected to the solid electrolyte layer 130. Furthermore, the solid electrolyte contained in the positive electrode active material layer 111 is in contact with the solid electrolyte layer 130, and is electrically connected to the solid electrolyte layer 130.

[0468] As a result, the positive electrode active material included in the positive electrode active material layer 111 is directly or indirectly electrically connected to the solid electrolyte layer 130 .

[0469] The laminate 100 can be manufactured as follows: for the solid electrolyte layer 130 provided on the positive electrode 110 as described above, the negative electrode 120 is laminated using a known method in such a manner that the negative electrode electrolyte layer 121 contacts the surface of the solid electrolyte layer 130. Thus, the solid electrolyte layer 130 and the negative electrode active material layer 121 are in contact and conduct with each other.

[0470] As described above, the obtained all-solid lithium ion battery 100 is provided in such a manner that the positive electrode 110 and the negative electrode 120 are not short-circuited, and the solid electrolyte layer 130 is in contact with the positive electrode 110 and the negative electrode 120. The provided all-solid lithium ion battery 100 is connected to an external power source, and is charged by applying a negative potential to the positive electrode 110 and a positive potential to the negative electrode 120.

[0471] Furthermore, the charged all-solid lithium ion battery 100 is discharged by connecting a discharge circuit to the positive electrode 110 and the negative electrode 120 and passing a current through the discharge circuit.

[0472] By using the positive electrode active material for an all-solid-state lithium-ion battery having such a structure, lithium ions can be smoothly transferred between the positive electrode and the solid electrolyte, thereby improving battery performance such as discharge rate characteristics.

[0473] The electrode constructed as described above has the above-mentioned positive electrode active material for all-solid-state lithium-ion batteries, so that the battery performance such as the discharge rate characteristics of the all-solid-state lithium-ion batteries can be improved.

[0474] The all-solid lithium ion battery having the above-described structure has the above-described positive electrode active material for an all-solid lithium ion battery and therefore exhibits excellent battery performance such as discharge rate characteristics.

[0475] The preferred embodiment of the present invention has been described above with reference to the accompanying drawings, but the present invention is not limited to this embodiment. The various shapes or combinations of the components shown in the above embodiment are examples, and various changes can be made according to design requirements, etc. without departing from the scope of the present invention.

[0476] As an aspect, the present invention also includes the following aspects: Hereinafter, "positive electrode active material T" refers to particles that satisfy all of the above formulas (1) to (3) and are formed of crystals containing a lithium metal composite oxide, wherein the lithium metal composite oxide has a layered structure and contains at least Li and a transition metal.

[0477] (2-1) Use of positive electrode active material T for all-solid-state lithium-ion battery.

[0478] (2-2) Use of positive electrode active material T for positive electrode of all-solid-state lithium ion battery.

[0479] (2-3) Use of positive electrode active material T for manufacturing all-solid-state lithium-ion batteries.

[0480] (2-4) Use of positive electrode active material T for producing a positive electrode of an all-solid-state lithium-ion battery.

[0481] (2-A) The all-solid-state lithium-ion battery is the use described in any one of (2-1) to (2-4) above, wherein the solid electrolyte includes an oxide-based solid electrolyte.

[0482] (3-1) Positive electrode active material T in contact with the solid electrolyte layer.

[0483] (3-1-1) The positive electrode active material T described in (3-1) above, wherein the solid electrolyte layer contains an oxide-based solid electrolyte.

[0484] (3-2) A positive electrode in contact with a solid electrolyte layer, the positive electrode comprising a positive electrode active material layer in contact with the solid electrolyte layer and a current collector on which the positive electrode active material layer is stacked, wherein the positive electrode active material layer contains a positive electrode active material T.

[0485] (3-3) A positive electrode, which is a positive electrode in contact with a solid electrolyte layer, the positive electrode having a positive electrode active material layer in contact with the solid electrolyte layer and a collector stacked with the positive electrode active material layer, the positive electrode active material layer comprising a positive electrode active material T and a solid electrolyte, the positive electrode active material T comprising a plurality of particles, and the solid electrolyte being filled between the plurality of particles and in contact with the particles.

[0486] (3-4) The positive electrode described in (3-3) above, wherein the solid electrolyte and the particles contained in the positive electrode active material layer are respectively in contact with the solid electrolyte layer.

[0487] (3-A) The positive electrode described in (3-2), (3-3) or (3-4) above, wherein the solid electrolyte layer contains an oxide-based solid electrolyte.

[0488] (3-B) The positive electrode described in (3-2), (3-3), (3-4) or (3-A) above, wherein the solid electrolyte contained in the positive electrode active material layer is an oxide-based solid electrolyte.

[0489] (3-5) An all-solid-state lithium-ion battery comprising the positive electrode active material T described in (3-1) or (3-1-1), or the positive electrode described in any one of (3-2), (3-3), (3-4), (3-A) and (3-B).

[0490] (4-1) A charging method for an all-solid-state lithium-ion battery, comprising: providing a solid electrolyte layer in contact with a positive electrode and a negative electrode in a manner such that the positive electrode and the negative electrode are not short-circuited; and applying a negative potential to the positive electrode and a positive potential to the negative electrode using an external power source, wherein the positive electrode comprises a positive electrode active material T.

[0491] (4-2) A method for discharging an all-solid-state lithium-ion battery, comprising: providing a solid electrolyte layer in contact with a positive electrode and a negative electrode in a manner such that the positive electrode and the negative electrode are not short-circuited; and charging the all-solid-state lithium-ion battery by applying a negative potential to the positive electrode and a positive potential to the negative electrode using an external power source; and connecting a discharge circuit to the positive electrode and the negative electrode of the charged all-solid-state lithium-ion battery, wherein the positive electrode contains a positive electrode active material T.

[0492] (4-A) The method for discharging an all-solid-state lithium-ion battery described in (4-1) above, or the method for discharging an all-solid-state lithium-ion battery described in (4-2) above, wherein the solid electrolyte layer comprises an oxide-based solid electrolyte.

[0493] Example

[0494] The present invention will be described below using examples, but the present invention is not limited to these examples.

[0495] <Composition Analysis of Positive Electrode Active Material>

[0496] The composition analysis of the positive electrode active material manufactured by the method described later is carried out by the method described in the <Composition Analysis>. In addition, the composition of the lithium metal composite oxide is obtained by performing a composition analysis of the positive electrode active material so that the obtained analysis result corresponds to the composition of the composition formula (A). That is, the values ​​of x, y, z and w obtained from the positive electrode active material described later are regarded as the values ​​of x, y, z and w of the lithium metal composite oxide.

[0497] <Method for Confirming Layered Structure>

[0498] Whether the lithium metal composite oxide contained in the positive electrode active material has a layered structure is confirmed by the above-mentioned <Method for Confirming Layered Structure>.

[0499] <Method for Confirming Particle Shape>

[0500] The shape of the particles contained in the positive electrode active material is determined by the method described in the above <Method for Confirming Particle Shape>. When the positive electrode active material includes a single particle, its content is determined by the above <Method for Calculating the Content of Single Particle>.

[0501] <Measurement of Particle Size Distribution>

[0502] The cumulative particle size distribution of the positive electrode active material was measured by the method described in the above-mentioned <Method for measuring cumulative particle size distribution based on volume standard>, and D 10 (μm), D 50 (μm), D 90 (μm), D max (μm), D min (μm) value.

[0503] From the obtained values, calculate D 90 / D 10 , D max / D min .

[0504] <Example 1>

[0505] (Manufacturing of Positive Electrode Active Material 1)

[0506] After water was placed in a reaction tank equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 50°C.

[0507] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution and a manganese sulfate aqueous solution were mixed in a ratio such that the atomic ratio of Ni to Co to Mn reached 0.88:0.08:0.04 to prepare a mixed raw material solution 1.

[0508] Next, the mixed raw material solution 1 and the ammonium sulfate aqueous solution are continuously added as a complexing agent into the reaction tank under stirring, and nitrogen is continuously ventilated into the reaction tank. In such a manner that the pH of the solution in the reaction tank becomes pH 12.4 when the temperature of the aqueous solution is 40° C., the sodium hydroxide aqueous solution is added dropwise at appropriate times to obtain nickel-cobalt-manganese composite hydroxide particles. The nickel-cobalt-manganese composite hydroxide particles are washed and dehydrated using a centrifuge. Thereafter, they are separated and dried at 120° C. to obtain nickel-cobalt-manganese composite hydroxide 1.

[0509] Next, the lithium hydroxide was pulverized using a dry continuous fine particle pulverizer and a dynamic mill (model MYD5) produced by Nippon Coke Industry, thereby obtaining pulverized lithium hydroxide 1 .

[0510] The pulverization conditions were as follows: a screw speed of 1000 rpm, a lithium hydroxide supply rate of 12 kg / hour, and 5.1 kg of φ5 mm alumina balls were added to perform pulverization.

[0511] Nickel-cobalt-manganese composite hydroxide 1, crushed lithium hydroxide 1 and potassium sulfate powder are weighed and mixed in a molar ratio of Li / (Ni+Co+Mn)=1.05 and K2SO4 / (LiOH+K2SO4)=0.1, and then sintered at 800°C for 10 hours in an oxygen atmosphere to obtain a mixture 1 containing lithium metal composite oxide.

[0512] Mixture 1 and pure water (water temperature 5° C.) were mixed in such a ratio that the ratio of mixture 1 to the total amount of mixture 1 and pure water was 30% by mass, and the resulting slurry was stirred for 10 minutes.

[0513] The slurry was dehydrated, and the solids were washed with pure water (liquid temperature 5° C.) twice the mass of the mixture 1 used to prepare the slurry (rinsing step). The solids were dehydrated again, vacuum dried at 80° C. for 15 hours, and then vacuum dried at 150° C. for 8 hours to obtain a positive electrode active material 1.

[0514] (Evaluation of Positive Electrode Active Material 1)

[0515] When the composition of the positive electrode active material 1 is analyzed and matched to the composition formula (A), x = 0.05, y = 0.08, z = 0.04, and w = 0. The crystal structure of the lithium metal composite oxide 1 contained in the positive electrode active material 1 is a hexagonal layered crystal structure belonging to the space group R-3m.

[0516] The SEM observation result of the positive electrode active material 1 showed that it consisted of a single particle (content ratio: 90% or more).

[0517] When measuring the particle size distribution of the positive electrode active material 1, (D 90 / D 10 ) is 10.32, D 50 5.79μm, D max 29.95μm, D max / D min It is 28.17.

[0518] Figure 3 The cumulative particle size distribution curve of the positive electrode active material 1 is shown.

[0519] <Example 2>

[0520] (Manufacturing of Positive Electrode Active Material 2)

[0521] After water was placed in a reaction tank equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 50°C.

[0522] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution and a manganese sulfate aqueous solution were mixed in a ratio of Ni:Co:Mn of 0.50:0.20:0.30 to prepare a mixed raw material solution 2.

[0523] Next, the mixed raw material solution 2 and the aqueous ammonium sulfate solution are continuously added as a complexing agent into the reaction tank under stirring, and nitrogen is continuously ventilated into the reaction tank. In such a manner that the pH of the solution in the reaction tank becomes pH 11.1 when the aqueous solution temperature is 40° C., the sodium hydroxide aqueous solution is added dropwise at appropriate times to obtain nickel-cobalt-manganese composite hydroxide particles. The nickel-cobalt-manganese composite hydroxide particles are washed and dehydrated using a centrifuge. Thereafter, they are separated and dried at 120° C. to obtain nickel-cobalt-manganese composite hydroxide 2.

[0524] Next, the lithium hydroxide was pulverized using a dry continuous fine particle pulverizer and a dynamic mill (model MYD5) produced by Nippon Coke Industry, thereby obtaining pulverized lithium hydroxide 2.

[0525] The pulverization conditions were as follows: a screw speed of 1000 rpm, a lithium hydroxide supply rate of 12 kg / hour, and 5.1 kg of φ5 mm alumina balls were added to perform pulverization.

[0526] Nickel-cobalt-manganese composite hydroxide 2 and lithium hydroxide powder were weighed and mixed in a molar ratio of Li / (Ni+Co+Mn)=1.05, and then calcined at 970° C. for 4 hours in an air atmosphere to obtain a positive electrode active material 2 .

[0527] (Evaluation of Positive Electrode Active Material 2)

[0528] When the composition of the positive electrode active material 2 is analyzed and made to correspond to the composition formula (A), x=0.05, y=0.20, z=0.30, and w=0. The crystal structure of the lithium metal composite oxide contained in the positive electrode active material 2 is a hexagonal layered crystal structure belonging to the space group R-3m. The composition ratio of the positive electrode active material becomes the same ratio as Ni:Co:Mn=0.50:0.20:0.30 as the input ratio according to the result of the positive electrode active material 1. The positive electrode active material 2 is also the same ratio as Ni:Co:Mn=0.50:0.20:0.30 as the input ratio. Therefore, theoretically, the composition of the positive electrode active material 2 becomes x=0.05, y=0.20, z=0.30, and w=0.

[0529] The SEM observation result of the positive electrode active material 2 showed that the positive electrode active material 2 contained primary particles and secondary particles but did not contain single particles.

[0530] When measuring the particle size distribution of the positive electrode active material 2, (D 90 / D 10 ) is 12.57, D 50 10.86μm, D max 37.74μm, D max / D min It is 12.59.

[0531] <Comparative Example 1>

[0532] (Manufacturing of Positive Electrode Active Material E1)

[0533] A commercial product of LiCoO2 (cellseed C-5H manufactured by Nippon-Chem Co., Ltd.) was evaluated as the positive electrode active material E1. As the positive electrode active material E1, a commercial product of LiCoO2 having a particle size distribution within the range of D50=5 μm±2 μm was used.

[0534] (Evaluation of Positive Electrode Active Material E1)

[0535] The SEM observation result of the positive electrode active material E1 showed that it consisted of a single particle (content: 100%).

[0536] When measuring the particle size distribution of the positive electrode active material E1, (D 90 / D 10 ) is 4.32, D 50 5.00μm, D max 13.39μm, D max / D min It is 7.94.

[0537] <Comparative Example 2>

[0538] (Manufacturing of Positive Electrode Active Material E2)

[0539] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution and a manganese sulfate aqueous solution are mixed in a ratio of Ni to Co to Mn of 0.91:0.07:0.02 to prepare a mixed raw material solution; and a sodium hydroxide aqueous solution is added dropwise at appropriate times in such a manner that the pH of the solution in the reaction tank becomes pH 12.3 when the temperature of the aqueous solution is 40°C. Except for this, a nickel-cobalt-manganese composite hydroxide 4 is obtained in the same manner as in Example 1.

[0540] Nickel-cobalt-manganese composite hydroxide 4 and lithium hydroxide powder were weighed and mixed in a molar ratio of Li / (Ni+Co+Mn)=1.26, and then calcined at 760°C for 6 hours in an oxygen atmosphere to obtain a positive electrode active material E2.

[0541] (Evaluation of Positive Electrode Active Material E2)

[0542] When the composition of the positive electrode active material E2 was analyzed and matched to the composition formula (A), x=0.02, y=0.07, z=0.02, and w=0.

[0543] The SEM observation result of the positive electrode active material E2 showed that it consisted of single particles (content ratio: 90% or more).

[0544] When measuring the particle size distribution of the positive electrode active material E2, (D 90 / D 10 ) is 14.01, D 50 7.68μm, D max 59.81μm, D max / D min It is 44.66.

[0545] <Manufacturing of all-solid-state lithium-ion batteries>

[0546] All-solid-state lithium-ion batteries were manufactured by the method described in the above-mentioned <Manufacturing of All-Solid-State Lithium-Ion Battery> using the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 and 2, respectively.

[0547] <Determination of 0.05CA / 0.01CA Discharge Capacity Ratio>

[0548] The 0.05CA / 0.01CA discharge capacity ratio of the all-solid lithium ion battery was measured by the method described in the above <Measurement of 0.05CA / 0.01CA Discharge Capacity Ratio>.

[0549] <Manufacturing of Liquid Lithium Secondary Batteries>

[0550] (Manufacturing of positive electrode for lithium secondary battery)

[0551] The positive electrode active material obtained by the above-mentioned manufacturing method, the conductive material (acetylene black) and the binder (PVdF) were added and kneaded in a ratio of positive electrode active material: conductive material: binder = 92:5:3 (mass ratio) to prepare a paste positive electrode mixture. NMP was used as an organic solvent when preparing the positive electrode mixture.

[0552] The obtained positive electrode mixture was applied to an Al foil with a thickness of 40 μm, which served as a current collector, and vacuum dried at 150° C. for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of ​​the positive electrode for a lithium secondary battery was 1.65 cm 2 .

[0553] (Manufacturing of lithium secondary battery (coin-type half-cell))

[0554] The following operations were performed in a glove box under an argon atmosphere.

[0555] The positive electrode for lithium secondary battery produced in (Production of positive electrode for lithium secondary battery) was placed on the lower cover of a coin-type battery R2032 component (produced by Hohsen Co., Ltd.) with the aluminum foil facing downward, and a separator (polyethylene porous film) was placed thereon.

[0556] 300 μl of an electrolyte solution was injected therein. The electrolyte solution used was a solution in which LiPF6 was dissolved in a mixed solution of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate at a ratio of 30:35:35 (volume ratio) so as to give a ratio of 1.0 mol / l.

[0557] Next, metallic lithium was used as the negative electrode, the negative electrode was placed on the upper side of the laminated film separator, a top cover was put on via a gasket, and riveted using a riveting machine to produce a lithium secondary battery (coin-type half cell R2032, hereinafter sometimes referred to as a "half cell").

[0558] <Determination of 0.05CA / 0.01CA Discharge Capacity Ratio>

[0559] Using the prepared half-cell, an initial charge and discharge test was carried out under the following conditions, and then a discharge rate test was carried out.

[0560] <Initial charge and discharge test conditions>

[0561] Test temperature: 25℃

[0562] Maximum charging voltage 4.3V, charging current 0.2CA, cut-off current 0.05CA, constant current constant voltage charging

[0563] Minimum discharge voltage 2.5V, discharge current 0.2CA, constant current discharge

[0564] <Discharge rate test>

[0565] Test temperature: 25℃

[0566] Maximum charging voltage 4.3V, charging current 1CA, constant current constant voltage charging

[0567] Minimum discharge voltage 2.5V, discharge current 0.2CA or 10CA, constant current discharge

[0568] The discharge capacity when it is discharged at a constant current of 0.2CA and the discharge capacity when it is discharged at a constant current of 10CA are used to calculate the 10CA / 0.2CA discharge capacity ratio obtained by the following formula as an indicator of the discharge rate characteristics. The higher the 10CA / 0.2CA discharge capacity ratio, the higher the discharge rate characteristics and the higher the output power of the lithium secondary battery.

[0569] 10CA / 0.2CA discharge capacity ratio (%) = discharge capacity at 10CA / discharge capacity at 0.2CA×100

[0570] <Evaluation Results>

[0571] The evaluation results are shown in Tables 1 and 2.

[0572] [Table 1]

[0573] <![CDATA[D 90 / D 10 ]]> <![CDATA[D 50 ]]> <![CDATA[D max ]]> <![CDATA[D max / D min ]]> Example 1 10.32 5.79μm 29.95μm 28.17 Example 2 12.57 10.86μm 37.74μm 12.59 Comparative Example 1 4.32 5.00μm 13.39μm 7.94 Comparative Example 2 14.01 7.68μm 59.81μm 44.66

[0574] [Table 2]

[0575]

[0576] As a result of the evaluation, all solid-state lithium ion batteries using the positive electrode active materials of Examples 1 and 2 showed excellent discharge rate characteristics, whereas the positive electrode active materials of Comparative Examples 1 and 2 had poor discharge rate characteristics.

[0577] When a liquid lithium ion secondary battery was prepared and evaluated for the positive electrode active materials of the examples and comparative examples, it was evaluated as shown in Table 2 that any of the positive electrode active materials could be used favorably.

[0578] Thus, even positive electrode active materials that work well in liquid lithium ion secondary batteries have great differences in discharge rate characteristics when made into all-solid lithium ion batteries. The positive electrode active material for the all-solid lithium ion battery of the present invention shows high discharge rate characteristics.

[0579] From the above, it can be seen that the present invention is useful. BRIEF DESCRIPTION OF THE DRAWINGS

[0581] 100…stacked body, 110…positive electrode, 111…positive electrode active material layer, 112…positive electrode collector, 113…external terminal, 120…negative electrode, 121…negative electrode electrolyte layer, 122…negative electrode collector, 123…external terminal, 130…solid electrolyte layer, 200…outer packaging body, 200a…opening, 1000…all-solid-state lithium-ion battery.

Claims

1. A positive electrode active material for an all-solid-state lithium ion battery, which is a positive electrode active material for an all-solid-state lithium ion battery formed of particles containing crystals of a lithium metal composite oxide, The lithium metal composite oxide has a layered structure and contains at least Li and a transition metal. The positive electrode active material for the all-solid lithium ion battery satisfies the following formulas (1) to (3): The positive electrode active material for the all-solid lithium ion battery is in contact with the solid electrolyte layer, 4.5≤D 90 / D 10 (1) 3.0μm≤D 50 ≤15.0μm (2) D max ≤40.0μm (3) in, In formulas (1) to (3), the particle diameters at which the cumulative proportions from the small particle side reach 10%, 50%, and 90% in the volume-based cumulative particle size distribution curve obtained by laser diffraction particle size distribution measurement are respectively designated as D 10 , D 50 , D 90 , D max is the maximum particle size in the cumulative particle size distribution curve, and its unit is μm. 2 . The positive electrode active material for an all-solid lithium ion battery according to claim 1 , which is used in an all-solid lithium ion battery containing an oxide-based solid electrolyte.

3. The positive electrode active material for an all-solid lithium ion battery according to claim 1 or 2, which satisfies the following formula (1)-1: 4.5≤D 90 / D 10 <14.0(1)-1。 4. The positive electrode active material for an all-solid-state lithium ion battery according to claim 1 or 2, wherein D 90 / D 10 It is 7.0~13.

0.

5. The positive electrode active material for an all-solid-state lithium ion battery according to claim 1 or 2, which satisfies the following formula (4): 8.0≤D max / D min ≤40.0 (4) in, In formula (4), D min is the minimum particle size in the cumulative particle size distribution curve, and its unit is μm.

6. The positive electrode active material for an all-solid lithium ion battery according to claim 1 or 2, wherein The transition metal is at least one element selected from the group consisting of Ni, Co, Mn, Ti, Fe, V and W.

7. The positive electrode active material for an all-solid-state lithium ion battery according to claim 6, wherein The lithium metal composite oxide is represented by the following formula (A): Li[Li x (Ni (1-y-z-w) Co y Mr z M w ) 1-x ]O2(A) Wherein, M is one or more elements selected from Fe, Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga and V, and satisfies -0.10≤x≤0.30, 0≤y≤0.40, 0≤z≤0.40, 0≤w≤0.10 and 0 <y+z+w。 8. The positive electrode active material for an all-solid-state lithium ion battery according to claim 7, wherein In the above formula (A), 1-yzw≥0.50 and y≤0.30 are satisfied.

9. The positive electrode active material for an all-solid lithium ion battery according to claim 1 or 2, wherein: The particles are composed of primary particles, secondary particles that are aggregates of the primary particles, and single particles that exist independently of the primary particles and the secondary particles. The content of the single particles in the particles is 20% or more. 10 . An electrode comprising the positive electrode active material for an all-solid lithium ion battery according to claim 1 . The electrode according to claim 10 , further comprising a solid electrolyte.

12. An all-solid lithium ion battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, The solid electrolyte layer includes a first solid electrolyte, The positive electrode includes a positive electrode active material layer in contact with the solid electrolyte layer and a current collector on which the positive electrode active material layer is stacked. The positive electrode active material layer includes the positive electrode active material for an all-solid-state lithium ion battery according to any one of claims 1 to 9.

13. The all-solid lithium ion battery according to claim 12, wherein: The positive electrode active material layer includes the positive electrode active material for an all-solid-state lithium ion battery and a second solid electrolyte.

14. The all-solid lithium ion battery according to claim 13, wherein: The first solid electrolyte and the second solid electrolyte are made of the same substance.

15. The all-solid lithium ion battery according to any one of claims 12 to 14, wherein The first solid electrolyte has an amorphous structure.

16. The all-solid lithium ion battery according to any one of claims 12 to 14, wherein The first solid electrolyte is an oxide-based solid electrolyte.

17. A positive electrode in contact with a solid electrolyte layer, the positive electrode comprising a positive electrode active material layer in contact with the solid electrolyte layer, and a current collector stacked with the positive electrode active material layer, the positive electrode active material layer comprising a positive electrode active material, the positive electrode active material being formed of particles comprising crystals of a lithium metal composite oxide, The lithium metal composite oxide has a layered structure and contains at least Li and a transition metal, and the positive electrode active materials all satisfy the following formulas (1) to (3): 4.5≤D 90 / D 10 (1) 3.0μm≤D 50 ≤15.0μm (2) D max ≤40.0μm (3) in, In formulas (1) to (3), the particle diameters at which the cumulative proportions from the small particle side reach 10%, 50%, and 90% in the volume-based cumulative particle size distribution curve obtained by laser diffraction particle size distribution measurement are respectively designated as D 10 , D 50 , D 90 , D max is the maximum particle size in the cumulative particle size distribution curve, and its unit is μm.

18. Use of a positive electrode active material formed of particles containing crystals of a lithium metal composite oxide in an all-solid lithium ion battery, The lithium metal composite oxide has a layered structure and contains at least Li and a transition metal, and the positive electrode active materials all satisfy the following formulas (1) to (3): 4.5≤D 90 / D 10 (1) 3.0μm≤D 50 ≤15.0μm (2) D max ≤40.0μm (3) in, In formulas (1) to (3), the particle diameters at which the cumulative proportions from the small particle side reach 10%, 50%, and 90% in the volume-based cumulative particle size distribution curve obtained by laser diffraction particle size distribution measurement are respectively designated as D 10 , D 50 , D 90 , D max is the maximum particle size in the cumulative particle size distribution curve, and its unit is μm.

19. Use of a positive electrode active material formed of particles containing crystals of a lithium metal composite oxide for a positive electrode of an all-solid lithium ion battery, The lithium metal composite oxide has a layered structure and contains at least Li and a transition metal, and the positive electrode active materials all satisfy the following formulas (1) to (3): 4.5≤D 90 / D 10 (1) 3.0μm≤D 50 ≤15.0μm (2) D max ≤40.0μm (3) in, In formulas (1) to (3), the particle diameters at which the cumulative proportions from the small particle side reach 10%, 50%, and 90% in the volume-based cumulative particle size distribution curve obtained by laser diffraction particle size distribution measurement are respectively designated as D 10 , D 50 , D 90 , D max is the maximum particle size in the cumulative particle size distribution curve, and its unit is μm.

Citation Information

Patent Citations

  • High density nickel hydroxide coprecipitated with cobalt and manganese, and method for producing the same

    JP2002201028A

  • Solid electrolyte composition, solid electrolyte-containing sheet, all-solid type secondary battery, and methods for manufacturing solid electrolyte-containing sheet and all-solid type secondary battery

    JP2018014317A

  • Reactor

    JP2020006335A

  • Handbasin

    WO043232

  • Positive electrode active material for lithium secondary batteries, positive electrode for lithium secondary batteries, and lithium secondary battery

    CN106463721A